Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 385603607 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false", "OccurrenceStatus is Present", "Year 1979-2007" ] } The dataset includes 385603607 records from 16927 constituent datasets: 16 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 420 records from Suivi des aires marines protégées de Moorea - Invertébrés benthiques. 2 records from New and little known species of Lepechinella (Crustacea, Amphipoda, Lepechinellidae) and an allied new genus Lepesubchela from the North Atlantic. 4 records from A revision of the species of the Neoserica (sensu lato) vulpes group (Coleoptera: Scarabaeidae: Sericini). 10 records from Analyses of the recent components of sediment core PS1277-1. 3167 records from MEXU/Leguminosae. 99 records from MIRC NAVFAC Incidental Sightings - Aerial 1965-2014. 3 records from The millipede family Polyxenidae (Diplopoda, Polyxenida) in the faunas of the Crimean Peninsula and Caucasus, with notes on other European Polyxenidae. 3 records from Potamotrygon boesemani (Chondrichthyes: Myliobatiformes: Potamotrygonidae), a new species of Neotropical freshwater stingray from Surinam. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 15 records from Inventaire des mammifères du Parc de la Haute-Île (93). 1 records from The neotype designation for Podismopsis gynaemorpha Ikonnikov, 1911 (Orthoptera: Acrididae). 144 records from Estimación de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 21 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 4 records from (Table 1) PBDE and BDE congener concentration in adipose tissue of East Greenland polar bears collected 1999-2001. 312 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 499 records from Range table from benthic foraminifers in ODP Hole 146-889A. 1897 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 130 records from Bulletin du Muséum d'Histoire Naturelle [1895- ]. 18 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 8334 records from SEWBReC Bees, Wasps and Ants (South East Wales). 1 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 5 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 107 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 4 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 1738 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 34 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 88 records from Total foraminifera counts of multinet M33/1_MSN1029. 756 records from Benthic foraminifera and algae abundance of Hole 81-552A. 6 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 12146 records from University of Guam Insect Collection. 2 records from Dermaptera of Iran with description of Euborellia angustata sp. nov.. 19 records from Dinoflagellate abundance of Hole 81-554. 216 records from Zoocenosis of the mole burrows in the forest zone of Western Siberia. 81 records from Museu de Ciències Naturals de Barcelona: BGJBB. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 1 records from A Scanning Electron Microscopy Study Of The Epiprocts Of Western North American Sweltsa (Plecoptera: Chloroperlidae). 158 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 2 records from Hydromedusae observed during night dives in the Gulf Stream. 296 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche (Plantas). 1305 records from Plasm bearing foraminifera counts during METEOR cruise M36/5. 251 records from UWIZM Molluscs. 26 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 1251 records from MCP-Aves - Coleção de Aves. 56 records from Plasm bearing foraminifera counts of multinet M12/3_MSN562. 100 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 143 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 55 records from Range table from planktonic foraminifers in ODP Hole 155-942C. 632 records from Bird specimens of Saitama Museum of Natural History. 73 records from orthopteracollections-nhmj-ioj. 55 records from Invasive alien species Impatiens glandulifera Royle in the Republic of Karelia. 317 records from Collections of Bioclass, school #179, Moscow. 159 records from (Fig. 5) Sea-surface temperature reconstructions of sediment core MD99-2304. 10994 records from BLM CETAP AIR Sightings. 341 records from Mycology collection, Norwegian Forest and Landscape Institute. 184 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 182 records from New Records of ground beetles for Colombia (Coleoptera: Carabidae). 11 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 1 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 2614 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 20 records from Range table from planktonic foraminifers in ODP Hole 144-874B. 7 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 197655 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 4 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 1 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 14 records from Brachymelecta Linsley, 1939, previously the rarest North American bee genus, was described from an aberrant specimen and is the senior synonym for Xeromelecta Linsley, 1939. 147 records from Range table from benthic foraminifers in ODP Hole 161-974B. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 2 records from UWIZM Anoles. 2547 records from Pat Livermore's Fungus Records 1976 - 2000. 1 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 399 records from Pollen analysis of sediment profile TR0 from Truennensee. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 2451 records from Macrobenthos Chukchi Sea, 1986. 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 84 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 374 records from Herbarium of the Institute of the problems of Northern development (TMN). 4 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 726 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 2 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 15 records from Tardigrad collection of the National Museum of Nature and Science. 1107 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 1120 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 140 records from Chronicle of Nature - Phenology of Mushrooms of Pechoro-Ilych State Nature Reserve. 2 records from The diversity of the genus Aricidea (Polychaeta: Paraonidae) from the Sea of Marmara, with descriptions of two new species and two new records for the Mediterranean fauna. 157 records from Orthoptera - SMF. 3371 records from FloVegSI-FAV - Faunistical database of ZRC SAZU. 231 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 26 records from HRC USWEX Aerial-Based Monitoring Surveys 2007. 1 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 59 records from Visual and genetic surveys for odontocete cetaceans in American Samoa 2003-06. 160 records from An updated checklist of aquatic plants of Myanmar and Thailand. 28 records from Phytoplankton abundance at station Casma_2003-01-30_2, Casma, Peru. 1263 records from BioGIS - Bryophytes - HUJ collections. 629 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 16388 records from Herbarium Universitatis Daugavpiliensis. 1011 records from SCANS II cetacean sightings on primary platform of vessel surveys 2005. 584 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 85 records from Planktic foraminifera counts at CTD station M39/4_402CTD-55. 2 records from Validation of Stenus (Hypostenus) primivenatus and Stenus (Hypostenus) yiae (Coleoptera, Staphylinidae, Steninae). 1 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 181 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 306 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5). 1 records from Megaluropidae *. 18906 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 101 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 37 records from Plecoptera. 23657 records from Swan Coastal Plain Survey. 5 records from New Species Of Neoperla Needham And Phanoperla Banks (Plecoptera: Perlidae) From The Philippine Islands. 80 records from Total foraminifera counts of multinet M21/4_MSN704. 4 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 66 records from New taxa and records of Gryllacrididae (Orthoptera, Stenopelmatoidea) from South East Asia and New Guinea with a key to the genera. 6 records from New findings on the Neotropical species Hermetia goncalvensi Albuquerque, 1955 (Diptera: Stratiomyidae): redescription, puparium, and geographical records. 290 records from Bees in the UVM Zadock Thompson Zoological Collection. 6 records from NZCS Brownsberg Nature Park Monitoring. 147 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 23527 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 1 records from NZCS Nassau Mountain Expeditions 2005/2006/2010/2014. 3 records from On the genus Systaria (Araneae: Clubionidae) in Southeast Asia: new species from caves and forests. 222 records from Neogene palynomorpha from site 81-552. 26 records from Huangilene, a new genus for the Miltochrista alikangiae (Strand, 1917) species-group, with descriptions of three new species from Indochina, continental China and Taiwan (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 782 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 842 records from RECORD Orthoptera Data. 7576 records from DFO Pacific Outside South Hard Bottom Longline Surveys. 2 records from A new genus and five new species of Neocoelidiinae leafhoppers from Brazil (Insecta: Hemiptera: Cicadellidae) with a key to males. 45 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 11777 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 9 records from Oberservation of birds at station PS14/143 along 49° West. 1265 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 2385 records from Upper Silesian Museum, Bird Observations. 118 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 108 records from Données naturalistes de Quentin ROME. 758 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 135 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 59 records from SEWBReC Springtails and allies (South East Wales). 3 records from Four new species of Phrynus, Lamarck (Arachnida: Amblypygi) from Mexico. 1549 records from Planktic foraminifera assemblage in sediment core SO42-74KL. 102 records from Benthic foraminifera abundance in ODP Leg 155 holes. 71517 records from The Himalayan Uplands Plant database (HUP Version 1). 90 records from Artenvielfalt auf dem Schulgelände. 370 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2007. 1241 records from National Museum of Natural Science. 126 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 135 records from Agencement temporel des populations et des peuplements d'invertébrés benthiques. 237 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 69 records from Global Ocean Sampling Expedition. 1 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from The Pygopleurus Motschulsky (Coleoptera: Scarabaeoidea: Glaphyridae) of mainland Greece: taxonomy, faunistics and ecological notes. 12 records from Collections ichtyologiques et herpétologiques (BOUM). 5516 records from Données naturalistes de Bruno OGER. 8536 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 2 records from First record of the genus Tanaostigma (Hymenopteraı Chalcidoideaı Tanaostigmatidae) from the Afrotropical region with description of three new species. 11 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 99 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 5355 records from NE Scotland fish records 1800-2010. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 336 records from Range table from planktonic foraminifers in ODP Hole 155-930B. 30 records from Happywhale - Humpback Whale in Indian Ocean. 2 records from South American Leaf-Cutter Bees (Genus Megachile) Of The Subgenera Rhyssomegachile And Zonomegachile, With Two New Subgenera (Hymenoptera: Megachilidae). 101 records from Foraminifera species abundances from tow TT011_7-MOC66. 57913 records from Fichier communal des ongulés. 6 records from Sächsische Schweiz (Pfaffenstein). 2 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 755 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 5 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 1648 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 25 records from Living Cirripedia. 473 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 84 records from Roter Berg Werdau (Leubnitz). 411 records from Données naturalistes de Charlotte PICARD. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 3215 records from University of Nebraska State Museum Birds Collection. 3467 records from University of California Santa Barbara Invertebrate Zoology Collection. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 3 records from Discovery of the male of Colletes yanruae from Yunnan, China (Hymenoptera: Apoidea: Colletidae). 116 records from Dinoflagellate cysts of ODP Hole 189-1172D. 120 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 14190 records from Entomology Collection at the Natural History Museum of Utah. 1876 records from 台灣花蓮沿海賞鯨活動鯨豚觀測紀錄 (The observation records from the activities of whale and dolphin watching in the offshore of Hualien, Eastern Taiwan). 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 938 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 40 records from makran-chabahar-arthropods. 602 records from NMML Small Cetacean Aerial Survey 1997. 169772 records from Locations of plants on dot distribution maps in the Flora of Siberia (Flora Sibiraea, 1987–1997). 47758 records from ALCB - Herbário Alexandre Leal Costa. 281 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 8544 records from Fish specimens of Kagoshima University Museum. 26 records from (Table T8) Occurrence of Neogloboquadrina pachyderma in ODP Hole 178-1098C. 545 records from UTEP Invertebrates (Arctos). 54 records from Revision of the crab-spiders of the genus Runcinioides Mello-Leitão, 1929 (Araneae, Thomisidae). 369 records from Fish occurrence in Kuban River basin. 59 records from Schulteich Freie Waldorfschule Darmstadt. 1 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 163 records from Relative abundance of coccosphere-units at site GIK23414. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 22052 records from CNIN/Abejas de México/Apoidea. 915 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P. 643 records from Flora útil del Municipio de la Huerta, Jalisco. 2198 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 57 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 823 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 12 records from A new species of Hypostomus Lacépède, 1803 (Siluriformes: Loricariidae) from the rio Tocantins-Araguaia basin, Brazil. 330 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 76 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 625 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 319947 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 401405 records from DATAVES. 2 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 8 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1994-D2. 4508 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 1380 records from The Broward College Insect Collection. 742 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 409 records from Distribution of nanoplankton at trap WR2. 1191 records from (Figure 6) Dinoflagellate cyst measured on sediment core AI07-12G. 3 records from First records of two flower bug genera from Myanmar (Hemiptera: Heteroptera: Anthocoridae: Anthocorinae: Oriini), with description of a new species of Bilia. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 120152 records from Fermanagh Flora. 27456 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 1 records from Transfer of two South American ant species from Tapinoma Foerster 1850 to Forelius Emery 1888 (Hymenoptera: Formicidae: Dolichoderinae). 345 records from Isle of Wight non-native invasive species. 10 records from Description of Bagarius vegrandis, a new species of sisorid catfish from Indochina (Actinopterygii: Siluriformes), with notes on the identity of Bagarius bagarius. 466 records from Weber State University Herbarium. 79 records from Molecular phylogeny of the genus Lasiopogon (Diptera: Asilidae) and a taxonomic revision of the bivittatus section. 609 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 57 records from The Australian Ciidae (Coleoptera: Tenebrionoidea): supplement. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 368 records from UNCW Aerial Survey 1998-1999. 351 records from Range table from planktonic foraminifers in ODP Hole 155-938A. 13 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 79 records from Diatom abundance of Hole 95-613. 912 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 29 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 2 records from Results of palynological analysis of Hole 302-M0004C. 1 records from New Species Of The Genus Oronoqua Fennah (Hemiptera: Auchenorrhyncha: Fulgoroidea: Issidae) From Inland Ecuador. 4542 records from Système d’Information Régional sur la Faune et la Flore - FNE Centre-Val de Loire - Données 2016. 1 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 23 records from Abundance of benthos infauna at station GIK23042-2. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 60 records from Streuobstwiese. 2315 records from SIM-Fungal records compiled by Joan Montón. 88513 records from Western Australian Museum provider for OZCAM. 352 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 3865 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 659 records from Benthic foraminifera counts of sediment core GIK23352-3. 423 records from Colección de mamíferos voladores y no voladores de la Universidad de Nariño. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 47 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 128 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 1465302 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 191868 records from NRW Regional Data: South East Wales Non-sensitive species. 8 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 709 records from (Appendix Table 3) Relative abundances of planktonic foraminiferal species in sediment core MD01-2390. 3 records from Virotia azurea (Proteaceae: Macadamieae), a striking new species endemic to New Caledonia and notes on V. francii and V. leptophylla. 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 1 records from Taxonomic novelties in Apocynaceae subfam. Asclepiadoideae from New Caledonia. 703 records from CEPEC herbarium - Centro de Pesquisas do Cacau - Herbário Virtual REFLORA. 145 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 1 records from A clarification of B. C. Seeman’s Malagasy species of Colea Meisn. (Bignoniaceae). 12 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1459 records from M. Gollop Collection. 95 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 72 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 164 records from Schulhof Gymnasium Hürth Bonnstrasse. 3 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 10 records from Grewia hispidissima Wahlert, Phillipson & Mabb., sp. nov. (Malvaceae, Grewioideae): a new species of restricted range from northwestern Madagascar. 11 records from Plant-parasitic nematodes of Republic of Karelia. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 453 records from Benthic foraminifera counts of sediment core PS1852-2. 2099 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 3012 records from Distribution of foraminifera of sediment core GIK23258-2. 1 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 3 records from Taenionema Jeanae, A New Species Of Stonefly From Southern California (Plecoptera: Taeniopterygidae). 5 records from Six new species of Orthochirus Karsch, 1892 from Iran (Scorpiones Buthidae). 8 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 11 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 130492 records from University of Minnesota Insect Collection. 249509 records from ARABEL - Arachnologia Belgica. 40206 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 412 records from Heinersdorfer Sumpfwiese. 1 records from Capnia Shasta, A New Species In The Californica Group From Northwestern California (Plecoptera, Capniidae). 10208 records from Arctic Species Trend Index (ASTI) : Marine. 48 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 23877 records from Wolli Creek Preservation Society Bird Survey. 552 records from (Table S2) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 167 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 121 records from Distribución histórica, prospección actual y áreas potenciales para reintroducir lobo mexicano (Canis lupus baileyi) en Durango, sur de la Sierra Madre Occidental, México. 18 records from Naturtag. 7 records from Integrative taxonomy of the genus Dyscolus (Coleoptera, Carabidae, Platynini) in Ecuadorian Andes. 8326 records from Herbier Louis-Marie (QFA) - Collection de lichens. 41 records from HRC CRC Small Vessel-Based Monitoring Surveys July 2006. 59 records from Matter enrichment of the macrofauna community of MAC station 13368-008. 67 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 2 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 5 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 2 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 1089 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 28 records from Swedish Malaise Trap Project (SMTP) - Dermaptera. 125 records from Total foraminifera counts of multinet M21/2_MSN650. 4 records from Colecção Entomológica IIA. 15998 records from MZFC/Coleccion de Aves. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR64. 27 records from DMNS Egg Collection (Arctos). 230 records from A taxonomic revision of the African genus Desplatsia Bocq. (Malvaceae - Grewioideae). 378 records from (Table 2) Nannofossil occurrence in ODP Hole 101-627B. 9720 records from Lepidopterous specimens of Yamagata Prefectural Museum. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 185 records from Happywhale - Humpback Whale in Arctic Ocean. 6 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 144 records from MLZ Bird Collection (Arctos). 4 records from Two new damselflies of the genus Idiocnemis Selys from Gulf Province, Papua New Guinea (Odonata: Platycnemididae). 1 records from The megadiverse fauna of Neotropical Cerambycidae (Coleoptera): Notes, descriptions, new records, new species, and revalidations. 126 records from Naturschutzgebiet Müchelholz (Mücheln). 166 records from Wiese am Waldrand (Gurtweil). 4 records from New records and updated distribution of the ant-like jumping spider genus Zuniga Peckham & Peckham, 1892 (Salticidae: Salticinae: Sarindini) in the Neotropics. 403 records from NMML Gulf of Alaska marine mammal survey 2003. 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 18 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 1902 records from Midden-Limburg Fish Ponds Survey. 18188 records from Herbarium Senckenbergianum (FR) - Fungi. 1825 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 209 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 160 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 3 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 491 records from Geometridae de France métropolitaine. 1640 records from (Figure 3) Stratigraphic distribution of planktonic foraminifera in the Neogene of ODP Hole 122-761B. 96 records from Planktic foraminifera counts at CTD station PS55/063. 6 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 150 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 2778 records from Leicestershire and Rutland Aculeate Records. 2144 records from SPC CoFish Invertebrates Observations Marshall Islands 2007. 24 records from Leiolima iberica, a new harvestman genus and species from the Iberian Peninsula (Arachnida, Opiliones, Sclerosomatidae). 1 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 455340 records from First Bird Atlas. 1 records from Revision of the Oriental subgenus Patrisaspilota Fischer, 1995 (Hymenoptera: Braconidae: Alysiinae: Orthostigma Ratzeburg, 1844) with description of a new species from Papua New Guinea. 1905 records from MMS Marine Mammal Survey, PNW 1989-1990. 1836 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 29 records from Ensemble des données Orthoptères. 9685 records from United Kingdom National Whale Stranding Database 1913-2008. 4 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 23 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 8 records from A New Perlodes Species And Its Subspecies From The Balkan Peninsula (Plecoptera: Perlodidae). 899 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 2. 6919 records from Odonata records from RSPB Reserves 1970-2009. 5 records from Données supplémentaires Atlas des Mammifères marins. 76 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 123 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 132 records from Abundance of radiolaria at station UT99-23-2. 987791 records from NBIS Records to December 2016. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 2661 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 2590 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 372 records from (Appendix E) Stable carbon and oxygen isotope composition of Globigerinoides sacculifera of ODP Hole 121-758B. 727 records from South American Antarctic Marine Biodiversity Literature. 1045 records from A grid database on vascular plant distribution in the Meshchersky National Park, Ryazan Oblast, Russia. 17 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 3 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 638 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 50 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 1 records from Thirteen new records of ferns from Brazil. 307 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 15 records from Meiofauna abundance in sediment core 54301-010. 2 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 16 records from Happywhale - Leopard seal in Southern Ocean. 1308 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 6762 records from NE Scotland other invertebrate records 1800-2010. 26 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 1784 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 9370 records from Données Entomologiques A. HORELLOU 1988-2018. 1 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 321 records from Foraminifera abundance of Hole 74-526A. 184 records from Dinoflagellate abundance of Hole 81-555. 1 records from Rediscovery of Glenurus incalis Banks (Neuroptera: Myrmeleontidae), and notes on the Brazilian species of Glenurus Hagen. 31 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 797 records from Relative abundance of Neogene nannofossils at ODP Site 165-998 from the Caribbean. 163 records from Records of Halicarcinus planatus at sub-Antarctic regions. 453 records from Herbier National de Guinée (HNG). 9 records from New records of Stenopygium Becker (Diptera: Dolichopodidae) from the Neotropical Region, and a key to species. 877 records from Iowa State University Fishes Collection. 404 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 3 records from Revision of Afrotropical Silky Lacewings (Neuroptera: Psychopsidae). 13302 records from Global compendium of Aedes albopictus occurrence. 1 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 88 records from Teich Berlin Wuhlheide. 7 records from On a collection of hydroids (Cnidaria, Hydrozoa) from the southwest coast of Florida, USA. 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 150 records from AKG-Gelände (Bensheim). 24 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 23 records from Benthic foraminifera abundance of Hole 93-603. 8439 records from WOLL AVH data. 1389 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 354 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 19 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 15 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 240 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 159 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 1355 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 9164 records from Colección de Peces de Agua Dulce del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P). 34 records from New species of Ochodaeus Dejean from Madagascar II (Coleoptera: Scarabaeoidea: Ochodaeidae). 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 478 records from HUEMG herbarium - Universidade do Estado de Minas Gerais - Campus Carangola - Herbário Virtual REFLORA. 3 records from Revision of the Genus Leptogomphus Selys in Borneo, including gene trees and a two marker molecular phylogeny (Odonata: Anisoptera: Gomphidae). 210 records from Lebensraum Gesamtschule (Langerwehe). 314 records from Foraminifera abundance of Hole 64-481. 2 records from Two new species of the genus Microlysias (Crustacea, Amphipoda, Tryphosidae) from Korean Waters. 332 records from Données des collections d'algues du MNHN. 1862 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-9. 1703 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 365 records from Coléoptères Silphidés du département du Loiret. 49 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 123 records from Total foraminifera counts of multinet M21/2_MSN648. 422108 records from NOAA AFSC North Pacific Groundfish Observer. 2255 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 2197 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2). 2 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 2380 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 64 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 100 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 27 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 115 records from Total foraminifera counts of multinet M21/4_MSN694. 2 records from Distribution of Quinqueloculina sp. in sediment core 12930-014. 1211 records from Insects, Outer Hebrides. 8 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 46 records from An der Ohm, (Wettsaasen). 48 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 703 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 4 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 1004 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 151 records from Total foraminifera counts of multinet M36/6_MSN1196. 12 records from Taxonomic revision of Ceropegia sect. Huernia (Asclepiadoideae, Apocynaceae) in Saudi Arabia with three new combinations. 1897 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 10 records from Ostracod species in Oligocene sediments of core CRP-3. 3 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 2997 records from MMS Seabird Ecology Study 1985. 4 records from Review of the genus Holostaspis Kolenati, 1858 (Acari: Laelapidae). 2 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 13 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 6 records from Asturodes Amsel (Lepidoptera: Crambidae: Spilomelinae): Three New Species From The Western Hemisphere And Food Plant Records From Area De Conservación Guanacaste, Costa Rica. 2508 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 11 records from Benthic macrofauna abundance of sediment core 13077-093. 251819 records from Phase 2 Lowland Grassland Survey of Wales. 150 records from Naturalis Biodiversity Center (NL) - Crustacea. 1 records from Brown algae specimens of Komatsu City Museum. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 185 records from Inventaire des odonates d'intérêt communautaire. 2 records from Sonerila konkanensis (Melastomataceae), a new species from South Goa, India. 149 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 6 records from Review of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) of Iran and adjacent territories. 59 records from Nannofossil abundance of Hole 73-521A. 874 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 3061 records from BioGIS - Vascular plants - Israeli Gene Bank. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1276-1. 2 records from Range table from planktonic foraminifers in ODP Hole 169-1038E. 3 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 207 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 101 records from Radiolaria assemblage in sediment core GIK23400-3. 1 records from Review the bamboo-feeding genus Arcofaciella Fennah, 1956 (Hemiptera: Fulgoromorpha: Delphacidae) with description of a new species from India. 526 records from Range table from benthic foraminifers in ODP Hole 151-913B. 198 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 1 records from An extraordinary new genus and species of Pseudachorutinae (Collembola: Neanuridae) from Colombia. 1723 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 124 records from Kirkliston Range stream monitoring. 1088 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 659 records from University of Cincinnati, Margaret H. Fulford Herbarium - Lichens. 1 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 6750 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 373 records from South Dakota State University, The Severin-McDaniel Insect Research Collection. 488 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Site 198-1213. 167 records from Vascular plants occurrences in Dokdo islands, Korea, based on herbarium collections and legacy botanical literature. 2763 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 60 records from Total foraminifera counts from M35/1_MSN1065. 1897 records from Marine Turtles. 466 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 5 records from The species of the bee genus Centris of the “ hyptidis group ” revisited with the description of Centris (Anisoctenodes) new subgenus (Hymenoptera: Apidae: Centridini). 125 records from Total foraminifera counts of multinet M21/2_MSN650. 27 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 10 records from Microzooplankton abundance and biomass at station NBP97-03-03-5. 3 records from Vermont Orthoptera Records from Historic Dot Maps. 145 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1244-2. 829 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 143 (N.S) n° 36 (1), 2008 - Données faune. 19752 records from Restauración y conservación de Isla Guadalupe. 9 records from Coleção de Coleoptera da Universidade de Brasília. 2183 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 98 records from Warnowtal (Rostock). 766 records from (Table 2) Distribution of benthic foraminifera on sediment core PS2138-1. 50 records from Chronicle of Nature - Phenology of Insects of Baikalsky State Nature Biosphere Reserve. 2 records from A new western Atlantic snapping shrimp of the Alpheus macrocheles group (Caridea, Alpheidae) revealed by morphological, molecular and color data. 1232 records from Marie-Victorin Herbarium (MT) - Bryophytes. 21 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 1 records from Three Echiniscidae species (Tardigrada: Heterotardigrada) new to the Polish fauna, with the description of a new gonochoristic Bryodelphax Thulin, 1928. 10 records from Bostryx tortoranus (Doering, 1879) species complex (Gastropoda: Stylommatophora: Bulimulidae), a review of taxonomy and distribution of endemic species from Argentina. 178258 records from National Benthic Inventory. 8 records from Phenological Center - Fishes (Murmansk). 109 records from Dinoflagellate cysts from sediment core PS1295-4. 111 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 1071 records from Phytoplankton abundance and species composition in the Gulf of Naples and the Gulf Salerno in November 1985. 183 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 6078 records from Scotland Otter Survey Database. 844 records from Intermountain Herbarium (fungi, not lichens), Utah State University. 131697 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 639 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 178 records from Benthic foraminifera and algae abundance of Hole 81-554. 42 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 321 records from Ornithological observations in the Kharkiv region of Ukraine. 13513 records from CAS Entomology (ENT). 24 records from Range table from benthic foraminifers in ODP Hole 178-1103A. 65584 records from Carnet B Lorraine. 1875 records from Naturalis Biodiversity Center (NL) - Pisces. 24 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 320 records from Marine algal (seaweed) flora of Formigas Islets, Azores. 387 records from Counting of benthic foraminifera of ODP Hole 182-1132B. 2 records from Eine neue Art der Gattung Quedius STEPHENS aus Syrien (Coleoptera, Staphylinidae, Staphylininae, Staphylinini, Quediina. 495 records from Radiolaria assemblage in sediment core GIK23414-6. 308 records from (Table 3) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-704A. 180 records from Myxomycetes collection of the University of Eastern Finland. 311 records from Données du/de la naturaliste Bottinelli Julien provenant de la base de donnée du SINP Île-de-France CETTIA. 63292 records from Seasearch Marine Surveys in England. 27 records from Planktic foraminifera abundance of Hole 84-566C. 38 records from The water mite genus Aspidiobates Lundblad, 1941 from Australia (Acari: Hydrachnidia: Hygrobatidae) with the description of two new species. 5 records from The Endemic Sulawesi Fish Genus Lagusia (Teleostei: Terapontidae). 9 records from Swiss Occurrence Records of Native Species of Various Faunal Groups. 2 records from The genus Stenoterommata Holmberg, 1881 (Araneae, Pycnothelidae) in the Cerrado and Atlantic Forest from Southeastern and Central Brazil: description of four new species. 789 records from Collection Trichoptera - SMF. 162 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 1 records from Happywhale - Arnoux's Beaked Whale in Southern Ocean. 12 records from The pholcid spiders of Sri Lanka (Araneae: Pholcidae). 110 records from Abundances of dinoflagellate cysts in sediment trap MST-9 (Appendix 1). 2331 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 1910 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 1 records from First record to Brazil of one genera and seven species of Psychodidae (Diptera) with further new records for 10 countries on the Neotropics. 1984 records from (Figure 5) Range chart of selected dinocysts and acritarchs of ODP Hole 104-642A. 23909 records from Arizona State University Hasbrouck Insect Collection. 54555 records from CCAMLR historic KRILL. 62 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 2642 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 8 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 12 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 156 records from Chironomid remains in the sediment sequence of Site PG1212. 1011 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 2274 records from Lista florística de la Costa Grande del estado de Guerrero. 132 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 54737 records from MDFRC macroinvertebrate survey. 167 records from Review of the Spirobolida on Madagascar, with descriptions of twelve new genera, including three genera of ' fire millipedes' (Diplopoda). 62 records from Amtsrain Apolda-Zottelstedt. 72 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 83 records from (Table 9) Relative abundance of calcareous nannofossil species across the Cretaceous/Paleocene boundary at ODP Hole 120-750A. 47074 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 4 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 27 records from A New Species Of Isoperla Banks (Plecoptera: Perlodidae) From The Southern Appalachians, With Notes On The I. Montana Group. 58 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB03 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 180 records from (Table 2) Range chart for planktonic foraminifers from ODP Hole 111-677B. 6695 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 98 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 9 records from Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 99 records from Dorfrand Mauderode. 122 records from (Table 2) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-543. 56 records from Shrews of Poland. 1 records from Archaeal 16S Ribosomal RNA RefSeq Targeted Loci Project. 5826 records from K-State Museum of Entomological and Prairie Arthropod Research. 6977 records from Inventario de Hymenóptera; parasítica en México. 327 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 4 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 6904 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 1 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases: Cliff-nesting Birds, priority conservation species: Complementary Observations - [2010-2014]. 659 records from (Table 15) Distribution of planktonic foraminifers in ODP Hole 108-666A. 705 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 4 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 1284 records from ConDidact Citizen Science Surveys - Amphibians 2007. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 32 records from Total foraminifera counts of multinet FCA97C_MSN1345. 1 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 1 records from Catalogue and description of the coccolithophores (Haptophyta, Coccolithophyceae), calcareous, scale-bearing microalgae, in New Zealand waters. 236 records from Lucanidae. 13 records from New species, synonymy and records of Endomia and Stenidius (Coleoptera: Anthicidae) from Asia. 25443 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 2 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 54 records from Birds Specimens of Akita Prefectural Museum. 1 records from Three endemic Aphaenogaster from the Siculo-Maltese archipelago and the Italian Peninsula: part of a hitherto unrecognized species group from the Maghreb? (Hymenoptera: Formicidae: Myrmicinae). 35602 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-81. 10 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 185 records from Size of planktic foraminifera at CTD station PS55/051. 792 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 3 records from Epiproct And Dorsal Process Structure In The Allocapnia Forbesi Frison, A. Pygmaea (Burmeister), And A. Rickeri Frison Species Groups (Plecoptera: Capniidae), And Inclusion Of A. Minima (Newport) In A New Species Group. 119 records from Whale catches in the Southern Ocean. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 10 records from Benthic macrofauna abundance of sediment core 13200-008. 1 records from On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico. 5758 records from ERBG AVH data. 22 records from CABI Africa Invasive and Alien Species data. 17026 records from River Biologists' Database (EPA). 3 records from Seven species of Pseudopecoeloides Yamaguti, 1940 (Digenea, Opecoelidae) from temperate marine fishes of Australia, including five new species. 72531 records from Tiroler Landesmuseum Ferdinandeum. 64 records from Phytoplankton abundance at station Rigel_1_2005-02 in Febraury 2005, Chipana, Chile. 36 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 11428 records from Communautés adventices des systèmes cotonniers du nord Cameroun. 26486 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 90 records from The genus Leptostylopsis of Hispaniola (Coleoptera, Cerambycidae, Acanthocinini). 125 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 174795 records from Marine benthic dataset (version 1) commissioned by UKOOA. 214 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1). 5229 records from European Moth Nights. 5665 records from The Dolphin Project. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 65 records from Range table from planktonic foraminifers in ODP Hole 177-1089D. 286 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 13 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 760 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 2 records from A revision of the Chilean Brachyglutini - Part 4. Revision of Achilia Reitter, 1890: A. puncticeps and A. approximans species groups, with description of seven new species (Coleoptera: Staphylinidae: Pselaphinae). 661 records from Etude floristique de la forêt marécageuse de Lokoli au Bénin. 79 records from Marine algal (seaweed) flora of São Jorge Island, Azores. 2 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 1036 records from BUND - Dassower See (Lübeck/Dassow). 34438 records from Données naturalistes de Monsieur François FOURNIER. 1 records from Five new species of Macrostomus Wiedemann and a checklist of Empididae (s. str.) (Diptera) from Bolivia. 912 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 26639 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 4 records from Sächsische Schweiz (Wehlener Gebiet). 8 records from A review of the Asian orb weaving spider genus Pronoides (Araneae: Araneidae). 6016 records from Arthur Chapman Observations. 557 records from Cuxhavener Küstenheiden. 688592 records from Hatikka Observation Database. 108 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 45 records from Range table from planktonic foraminifers in ODP Hole 183-1139A. 1 records from Données naturalistes de Monsieur JOURDE Rémi. 106903 records from inatura - Erlebnis Naturschau Dornbirn. 168 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 581 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 130 records from Total foraminifera counts of multinet M21/6_MSN784. 9 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 48 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 16 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 15 records from (Table S2) Nannofossil abundances at DSDP Hole 86-577A. 60 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 151 records from Inventaire et regroupement de données Natura 2000. 1260 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 78074 records from Données de la flore d’Alsace (SBA). 486 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 1 records from Two new Afrotropical genera of Scatopsidae (Diptera). 1978 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 122 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 2 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 160 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 3752 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 51 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/009-2. 24 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 4 records from Begonia henrilaportei Scherber. & J. Duruisseau (Begoniaceae), a new endemic species from the Masoala peninsula, Madagascar. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_3-CTD39. 1666 records from Distribution of major planktic foraminifer at Site 177-1090. 121 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB02 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 102 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 8 records from Revision of Pseudexogone Augener, 1922 (Annelida, Polychaeta, Syllidae), and its transfer to Pilargidae. 77081 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 6 records from Range table from planktonic foraminifers in ODP Hole 151-912A. 2 records from Two new sponge-associated Branchiosyllis (Annelida: Syllidae: Syllinae) from Northeastern Brazil. 3402 records from (Table 10) Eocene-Oligocene diatom biostratigraphy of ODP Hole 120-748B. 495 records from Données naturalistes de Loïc SALAUN. 1477 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 754001 records from Flore Franco-Belge. 6514 records from EAC - Herbário Prisco Bezerra. 2507 records from East Ayrshire Species Database. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 1136 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 1485 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 18 records from Sarcodine counts and carbon biomass at station TT011_6-CTD71. 722 records from Leif Richardson Vermont Bee Specimens. 3 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 153 records from Benthic macrofauna abundance of subcores of sediment core 13078-015. 2139 records from Collection Crustacea - ZMB. 222 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 346 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 12 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 266 records from Structure of waterbird assemblages in fragmented coastal wetlands of Northeastern Algeria. 66 records from Plasm bearing foraminifera counts from multinet SO119_MSN1284. 1 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 2 records from Description of a new genus and four new species of Acaricalini (Acari, Eriophyidae, Phyllocoptinae) from South China. 1 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 2079 records from (Table 3B) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572C and 85-572D. 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 3 records from Polycentropus dinkinsorum (Trichoptera: Polycentropodidae), a newly described caddisfly species from the southern Appalachian Mountains, USA. 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 87 records from Microzooplankton abundance measured on water bottle samples at station PS65/514-2. 17 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 142 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 2310 records from (Table 2) Relative abundance of benthic foraminifera in sediment core CD17-30. 10 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 27 records from Review of the batfish genus Halicmetus Alcock, 1891 from Australian waters, with descriptions of two new species (Lophiiformes: Ogcocephalidae). 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 32642 records from The national database for marine data (MADS). 37 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 1948 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 3 records from Revision of the Agrilus wittemani species - group (Coleoptera: Buprestidae: Agrilini) with description of three new species from India and Myanmar. 74 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 97 records from Size of planktic foraminifera at CTD station M39/4_402CTD-55. 47 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 63-125 µm fraction. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 13 records from Warnowufer Groß Klein. 165 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 1384 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 1230 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 237 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocapra americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 44032 records from Alterra (NL) - Entomofauna inventory in peat swamps. 1084 records from Leicestershire and Rutland Mature trees Inventory 2011. 331 records from Pollen data of trap CB4. 20 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-11-5. 10 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0004C. 2 records from A new species of Glyphocrangon (Crustacea, Decapoda, Caridea, Glyphocrangonidae) from the Austral Islands, French Polynesia. 3 records from Two new endangered species of Polygala series Trichospermae (Polygalaceae), endemic to the Cerrado domain, Tocantins State, Brazil. 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 1 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 11 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 98 records from Nannofossil abundance of Hole 67-499B. 3927 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 1851 records from Colección de Geraniales hasta Lamiales del Museo Botánico CORD - IMBIV. 117 records from Surveys of the East Coast Akalat, Sheppardia gunningi, in Arabuko-Sokoke Forest, 2005-2011. 2 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 5 records from Integrative description of new giant pill-millipedes from southern Thailand (Diplopoda, Sphaerotheriida, Zephroniidae). 94 records from Marine algal (seaweed) flora of Faial Island, Azores. 178 records from Re-examination of the reef corals of Cocos (Keeling) Atoll, Charlie Veron. 101 records from Naturgrundstück (Eutin). 4 records from Taxonomy of Probolodus Eigenmann, 1911 (Characiformes: Characidae) with description of two new species, and comments about the phylogenetic relationships and biogeography of the genus. 2385 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene of ODP Hole 105-645E (Table 1). 7 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 150 records from données araneologiques de LEENKNEGT Virginie. 992 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 32 records from Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae). 22212 records from Données de l'Observatoire de la Faune de Bourgogne. 848 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 1981 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 677 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 97 records from Phenological Center - Birds (Murmansk). 7 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 67 records from Mammals of the Natural Laboratory of Peat-Swamp Forest, Sebangau, Central Kalimantan, Indonesia. 20 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 36 records from Sarcodine counts and carbon biomass at station TT012_5-PMOC5. 62 records from Echinoderms from the Seaflower Biosphere Reserve. 100 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 1 records from A review of the genera Anasillomos Londt, 1983, Oratostylum Ricardo, 1925, and Remotomyia Londt, 1983, with description of a new genus and two new species (Diptera: Asilidae: Stenopogoninae). 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 73 records from (Appendix A) Sea surface temperture reconstruction for ODP Hole 117-723A. 74772 records from Allan Herbarium (CHR). 17 records from Analyses of the recent components of sediment core PS1011-1. 30253 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 13 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 13503 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 4 records from Odonata Specimens of Yamaguchi prefectural Yamaguchi Museum. 4 records from MVZ Herp Observations (Arctos). 306 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 49 records from Phytoplankton abundance at station Rigel_5_2005-02 in Febraury 2005, Chipana, Chile. 279 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 80 records from Abundance of planktic foraminifera at CTD station PS55/080-1. 1680 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 150 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 333 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 23654 records from Plan de vertebrados de la Patagonia. 5 records from On the genus Gastrodynerus Bohart, 1984 (Hymenoptera: Vespidae: Eumeninae). 2954 records from Distribution of planktic foraminifera of sediment core M35003-4. 11813 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (FCME_AL). 735 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 107 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 27241 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 6 records from Distribution of Aphrocallistes beatrix in the N. Atlantic. 975 records from Danielsberg (Mölltal, Kärnten). 58 records from LPO_PACA_2017_12_18. 164 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 9 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 164 records from Pachliopta butterfly specimens at Museum Zoologi Bogor, Indonesia. 10825 records from Census of species recorded during phytosociological surveys in Benin. 1756 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 589 records from (Table 3) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-707A. 391 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 6194 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 2952 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 1 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 4633 records from Collection Pisces SMF. 178 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB02 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 10086 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 11 records from NMML Harbor Porpoise Aerial Survey, Cook Inlet, 1991. 735 records from MEXU/Tipos de plantas vasculares. 9 records from Swedish Malaise Trap Project (SMTP) - Bethylidae. 13125 records from données aranéologiques de CORNIC Jean-François. 2424 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 69 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1389. 1635 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 1313 records from Diatom assamblage in samples from sediment trap OG5. 1414 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 463 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 5 records from A taxonomic revision of the Palaearctic members of the Formica rufa group (Hymenoptera: Formicidae) - the famous mound-building red wood ants. 1193 records from NEFSC North Atlantic Marine Mammal and Turtle Aerial Abundance Survey 2007. 2454 records from Données issues du dispositif de Biosurveillance des Retombées Atmosphériques Métalliques par les Mousses (BRAMM). 1 records from Distributional and taxonomic notes on the crab spider genus Talaus Simon, 1886 with description of a new species (Araneae: Thomisidae). 695232 records from MICROBIS database. 1 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 123 records from Birdrace-Professorenteam-Münster. 14619 records from Ontario Breeding Bird Atlas 1981-1985. 3022 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 237988 records from Swiss National Grasshoppers Databank. 244 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 64 records from Planktic foraminifera counts at CTD station PS55/083-1. 25246 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 133 records from Pollen profile II/B at Krumbach, Germany. 7776 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 1882 records from Weevil and Bark Beetle records via iRecord. 16 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 31 records from Nationalpark Harz Schul-AG Braunlage. 6 records from Astyanax ajuricaba: a new species from the Amazon basin in Brazil (Characiformes: Characidae). 7 records from A new apterous rove beetle genus (Coleoptera: Staphylinidae) from the Northern Andes with an assessment of its phylogenetic position. 677 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 321 records from POPA- Fisheries Observer Program of the Azores: Marine mammal sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 1021 records from Phytocenoteca of the laboratory of ecosystem theory (Plants). 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 55 records from Phytoplankton abundance at station Sechin_2003-07-15_2, Casma, Peru. 367 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 144 (N.S) n° 37 (2), 2009 - Données faune. 173 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 18 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 1998 records from (Table 1) Dinoflagellate range chart of ODP Hole 120-748C. 99014 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 860 records from Taxa occurrences and composition of benthic macroinvertebrates from biodiversity surveys on Lake Victoria, Uganda (2001-2006). 58 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 3 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 74 records from pbzt_insect_biodiversity. 217 records from NZCS Upper Tapanahony Expedition 1991. 140 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 1 records from Ovomanonychus, a new genus of South American Sericoidini (Coleoptera Scarabaeidae: Melolonthinae). 804 records from Phytoplankton abundance in surface water in November 1997, Pisco, Peru. 5 records from A review of the Indian species formerly assigned to the genus Storena Walckenaer, 1805 (Araneae: Zodariidae) with the description of a new genus. 5 records from Description of a new species of the Lissochlora albociliaria species group (Lepidoptera: Geometridae, Geometrinae). 51 records from Coleção de Nematoda do Museu Nacional - UFRJ. 4497 records from Inventory of plant species through Benin (West Africa). 550 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 69 records from Total foraminifera counts of multinet M21/5_MSN731. 14 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 2 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 966 records from Planktic foraminifera abundance of Hole 72-516F. 1648 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 21 records from Two new trans-Andean species of Imparfinis Eigenmann & Norris, 1900 (Siluriformes: Heptapteridae) from Colombia. 1 records from Benthic foraminifera abundance of Hole 96-624. 486 records from HDCF herbarium - Universidade Federal de Santa Maria - Herbário Virtual REFLORA. 2 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 263 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 6 records from Range table from planktonic foraminifers in ODP Hole 183-1136A. 1 records from A new species of Hieracium sect. Pannosa (Asteraceae) from Bulgaria. 1999 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 3 records from Nouveautés dans le genre Lomariopsis Fée (Pteridophyta, Lomariopsidaceae) à Madagascar: trois espèces nouvelles et une espèce africaine nouvellement signalée. 2612 records from Fungi specimens of Saitama Museum of Natural History. 3 records from A New Species Of Perlesta (Plecoptera: Perlidae) From New York. 21 records from Cape Verde (Cabo Verde) 2005: Loggerhead Turtles (aggregated per 1-degree cell). 82 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 19 records from Siphonoecetinae (Crustacea: Amphipoda: Ischyroceridae) 7: Australian Concholestids, Ambicholestes n. gen., with a Description of Six New Species, and a New, Restricted Diagnosis for Caribboecetes Just, 1983. 138 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 631 records from Planktic foraminifera abundance of Hole 72-518. 27 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 51 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 605 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 61 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 214 records from Mammals in the collection of Zoological Museum of NSNHM (the National Science and Natural History Museum at the National Academy of Sciences of Ukraine, Kyiv): Erinaceidae, Talpidae, Soricidae, Myoxidae, Sminthidae. 327 records from Bosque Mesófilo de Montaña de México. 25 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 2 records from Amphibian specimens of Obihiro Centennial City Museum. 13367 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 5 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 638 records from Colección de Boraginales y Brassicaless del Museo Botánico CORD - IMBIV. 42721 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 600 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 1 records from University of Sindh Jamshoro Herbarium. 602 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 1 records from A New Genus of the Spider Family Caponiidae (Araneae, Haplogynae) from the West Indies. 1056 records from Chrysomelidae beetle data from iRecord. 17 records from Bryozoa, Brachiopoda and Entoprocta (TSZBr) UiT Tromsø Museum. 420 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 9920 records from 18S Monterey Bay Time Series: an eDNA data set from Monterey Bay, California, including years 2006, 2013 - 2016. 6 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 414 records from Registros Primates Neotropicales Convocatoria APC. 2 records from On three new species of Elpidium Müller, 1880 and the re-description of Elpidium laesslei (Tressler, 1956) from Jamaica (Ostracoda: Podocopida: Limnocytheridae). 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 1 records from Six new species of Macellicephala (Annelida: Polynoidae) from the Southern Ocean and south Atlantic with re-description of type species. 78 records from Planktic foraminifera counts at CTD station PS55/079-1. 531 records from MHA Herbarium: Collections of mosses from Yana-Indigirka Region, Yakutia, Russia. 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 111 records from Birdrace-Uhulogen-Lippe. 11 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 952 records from La familia Asclepiadaceae en México. 1 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 70 records from Swedish Malaise Trap Project (SMTP) - Odonata. 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 17 records from Four new species of Plega Navás, 1928 (Neuroptera: Mantispidae) from Mexico. 370 records from Otter survey of Ireland 2004 & 2005. 1039 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 2128 records from (Table T7) Calcareous nannofossil stratigraphy of ODP Hole 198-1210B. 6 records from Happywhale - Gray Whale in North Pacific Ocean. 18449 records from Suivi Temporel des Rhopalocères de France (STERF). 5 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 11 records from Cellaria (Bryozoa, Cheilostomata) from the deep: new species from the southern Zealandian region. 2 records from A new species of Plurellidae (Ascidiacea: Phlebobranchia) from Papua New Guinea. 177 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 128 records from Total foraminifera counts of multinet POS247/2_MSN1386. 3 records from Confirmation of Gonioctena rufa (Kraatz, 1879) (Coleoptera: Chrysomelidae) in northeastern Asia, previously misinterpreted as a subspecies of G. viminalis (Linnaeus, 1758), and a new synonym in the genus. 13 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 364 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 9781 records from CSIRO, fish surveys by the Soela, 1980s. 1 records from First record of a living ditaxiporine catenicellid in the Atlantic, with a description of Vasignyella ovicellata n. sp. (Bryozoa). 50 records from Bryophyte speciments of Toyota City Nature Sanctuari (TCNS).. 5 records from Three new species of deep-sea Gromia (Protista, Rhizaria) from the bathyal and abyssal Weddell Sea, Antarctica. 342 records from Nannofossil abundance of Hole 78-543. 9 records from Review of the species of the genus Serrapinnus Malabarba, 1998 (Teleostei: Characidae: Cheirodontinae) from the rio Tocantins-Araguaia basin, with description of three new species. 6379 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 362 records from Glasgow Museums BRC: Chrysomelidae. 13 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 2 records from The deep-water Calappidae, Matutidae and Leucosiidae of the Solomon Islands, with a description of a new species of Euclosia Galil, 2003 (Crustacea, Decapoda, Brachyura). 23 records from Total foraminifera counts of multinet FCA97C_MSN1339. 28 records from Bryde’s whales off eastern Venezuela - Vessel 1978-1979. 2591 records from USAC Mammals Collection. 361 records from Nannofossil abundance of Hole 66-490. 135 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 193 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100500. 111 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 1 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 2147 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 478 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 445 records from (Table 14) Distribution of planktonic foraminifers in ODP Hole 108-665A. 50 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018. 1 records from Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 174 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 1 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 1521 records from Données naturalistes de Bernard Lalanne-Cassou. 78 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 820 records from Nannofossil abundance of Hole 82-558A. 788 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 286 records from Données de collection de l'inventaire des Papillons de jour de Martinique. 1 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 3320 records from BioGIS - Mammals - SPNI. 7 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 510 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 16130 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 18 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 160 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 861 records from (Table 1) Percentage of Coccolithus pelagicus vs. Reticulofenestra spp. of ODP Hole 120-747A. 274097 records from SEWBReC Birds (South East Wales). 34 records from Lepidoptera of Mordovia State Nature Reserve. 130 records from Total foraminifera counts from multinet SO119_MSN1285. 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 29 records from Cethosia myrina butterfly specimens at Museum Zoologi Bogor, Indonesia. 49 records from DECAF - AUTEC Sperm Whales - Multiple Sensors - Samples. 1970 records from Dipterists Forum: Field Week 1981 (Kent). 1570 records from MEXU/Flora de Oaxaca. 8807 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 185 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 5061 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 207 records from Nannofossil abundance of Hole 66-488. 2 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 83 records from Heavy minerals of sediment core PL94-64. 96860 records from Amphibiens et Reptiles de France (Enquête 2). 520 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 84 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 1 records from New species of Adeonellopsis (Bryozoa: Adeonidae) from southern Zealandia and the western Tasman Sea. 113 records from Données naturalistes d'Alain BERLY. 14757 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 8 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 137 records from Données opportunistes. 1698 records from Red-throated diver national surveys in Scotland - raw data. 1960 records from (Figure 7) Distribution chart of benthic foraminifers in ODP Site 126-793. 368 records from Ring ouzel national sample survey in the UK in 1999. 1 records from Happywhale - Crabeater Seal in Southern Ocean. 11 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 1 records from Collection ornithologique A. Maës. 401 records from Planktic foraminifera distribution of sediment core SU81-07. 1 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 926 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 29 records from Mammal specimens of Komatsu City Museum. 33 records from A review of the genus Hexachaetoniella Paschoal in Australia (Acarina: Cryptostigmata: Pedrocortesellidae). 1 records from A new species of Philorhizus Hope, 1838 from Greece (Coleoptera, Carabidae, Lebiini). 41 records from Örtzemündung (Stedden). 19192 records from National Stag Beetle Surveys (Great Stag Hunts). 1734 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 466 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 48976 records from Marine Offshore Seabed Survey data held by JNCC. 12 records from Benthic foraminifera abundance of Hole 96-620. 99 records from Nanoplankton abundance at station GeoB2006-4. 1 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 22 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 416 records from Données du naturaliste Marquet Jacques provenant de la base de donnée du SINP Île-de-France CETTIA. 8585 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Entomologica). 94292 records from Herbarium of Taiwan Forestry Research Institute. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 23 records from Ackerrain Plönhagen. 172 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 1004 records from Données odonates. 188 records from Malawi-Histeridae-Biodiversity-Data. 13418 records from Swiss National Diplopoda Databank. 10604 records from Collections of Phytoplankton at Herbarium Berolinense, Berlin (B). 249 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 19 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 2 records from First record of the family Bolitophilidae (Diptera: Sciaroidea) from the Lagunas de Zempoala National Park, Mexico, with description a new species. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 34 records from Microzooplankton abundance and biomass at station TT043_4-1. 107 records from Distribution of seabirds at sea in the Gulf of Carpentaria, Australia (1990-1991). 424 records from Collection de C.C.H. Jongkind aux Monts Nimba. 1 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 2 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 5 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 2193 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 7 records from A review of the ant genus Metapone Forel from Madagascar.. 58 records from Phytoplankton abundance at station Casma_2003-03-27_2, Casma, Peru. 2 records from Afrotropical flower flies (Diptera: Syrphidae). A new genus and species from Kenya, with a review of the melanostomine group of genera. 7 records from Rosa gallica L. in "Medobory" Nature Reserve. 12 records from New species and additional records of Cephalocousya and Drepasiagonusa from China and Russia (Coleoptera: Staphylinidae: Aleocharinae: Oxypodini). 40 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, 30-63 µm fraction. 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 2834 records from Northern Gulf of Mexico Hypoxia can Alter Sediment Communities of Nitrifying Archaea. 38 records from Numbers and statistics of benthic foraminiferal Q-mode assemblages for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 2056 records from Flora vascular acuática de la cuenca del Río Tamesí. 15 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 375 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 4962 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 451 records from Patterns of abundance and size of dictyoceratid sponges among neighbouring islands in central Torres Strait (CRC-TS Project: Task Number T1.6a) 2005. 1 records from Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia. 501 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part III. 513 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 7799 records from Andes to Amazon Biodiversity Program. 51 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 13 records from Données naturalistes de Stéphane ORIO. 168 records from Inventario herpetofaunístico del noroeste de Hidalgo. 244 records from WildesMoor bei Schwabstedt. 379 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 1 records from Three new species of jumping spiders of the genus Hypaeus Simon, 1900 from Colombia (Salticidae: Salticinae: Amycini). 9366 records from ZooplanktonBeaufortSeaNOGAP2. 2 records from More than just the number of denticles: morphometric and limb variability in Neotropical cladoceran Alonella dadayi (Crustacea: Cladocera: Chydoridae). 1108 records from SWFSC Marine Mammal Survey, STAR 2003, Cruise 1623. 58 records from Hermit crabs of the family Parapaguridae (Crustacea: Decapoda: Anomura) from Australia: species of Strobopagurus Lemaitre, 1989, Sympagurus Smith, 1883 and two new genera.. 145 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 12 records from Microzooplankton abundance and biomass at station NBP97-08-23-6. 98 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 2 records from Albury Wodonga Nature Map. 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-093. 2176 records from Jardín Botánico Atlántico, Gijón: JBAG. 36 records from Microzooplankton abundance and biomass at station TT045_26-3. 1419 records from Diversity of algae in wetlands. 1 records from Description of a new species of the Ponerine ant genus, Emeyopone (Hymenoptera: Formicidae) from Karnataka, India.. 1680 records from Données rhopalocères collectées par le CEN Aquitaine entre 1970 et 2015. 587 records from Range table from planktonic foraminifers in ODP Hole 157-954A. 338 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 72 records from Données sur les Opisthobranches et Planaires de Mayotte. 1137 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 523 records from Range table from benthic foraminifers in ODP Hole 189-1169A. 106 records from Planktic foraminifera abundance of Hole 94-611. 3 records from Abundance of zooplankton in the Aral Sea. 67 records from Fish Fauna of Berlin. 3 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 1389 records from Phytoplankton abundance in surface water during cruise CD61. 1511 records from Kherson State University herbarium (KHER), Department of Botany. 29 records from Total foraminifera counts of trap L3_92_45. 334 records from Inventaire des Coléoptères Longicornes des Antilles françaises. 5474 records from Nijmegen Natural History Museum (NL) - Herbarium. 16 records from The Sphecid wasps of the genus Cerceris LATREILLE, 1802 of the " Biologiezentrum Linz " - Collection in Linz, Austria, from Subsaharan Africa and Madagascar, with description of five new species (Hymenoptera, Apoidea, Crabronidae). 66 records from Checklist of decapod crustaceans from the coast of the São Paulo state (Brazil) supported by integrative molecular and morphological data: IV. Infraorder Anomura: Superfamilies Chirostyloidea, Galatheoidea, Hippoidea and Paguroidea. 1591219 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 3 records from Département_du_Var_2017_12_18. 8 records from Microzooplankton abundance and biomass at station TT054_7-18. 106 records from Total foraminifera counts of trap L2_92_A42. 37 records from MIRC NAVFAC Incidental Sightings - Vessel 1965-2014. 40 records from Revision of the squat lobsters of the genus Leiogalathea Baba, 1969 (Crustacea, Decapoda, Munidopsidae) with the description of 15 new species. 32 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 5 records from Planktic foraminifera counts of multinet M21/4_MSN724. 1 records from Review of the genus Paradonus Stibick, 1971 (Elateridae: Negastriinae), with three new North American species. 21471 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 5 records from A new western Canadian record of Epeoloides pilosulus (Cresson). 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 657 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 30 records from Eusocial wasp fauna of Sulawesi Island, the central island of Wallacea (Hymenoptera: Vespidae; Polistinae, Vespinae). 2038 records from Table A3. Benthic foraminifera assemblage of sediment core GeoB1710-3. 33419 records from WADFW PSAMP W1993. 4 records from The Unicorn exists! A remarkable new genus and species of Perilissini (Hymenoptera: Ichneumonidae) from South East Asia. 7 records from Hyobanche thinophila (Orobanchaceae), a new species from the Western Cape of South Africa. 16 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 111 records from University of Algarve and ICNB Cetacean Sightings 1999. 5 records from Annales de la Société entomologique de France [1832- ]. 43 records from Type specimens in the Port Elizabeth Museum, South Africa, including the historically important Albany Museum collection. Part 2: Reptiles (Squamata). 57 records from Earthworms of mole burrows in the forest zone of Western Siberia. 200 records from Distribution of planktic foraminifera (250-500 µm) of sediment core GIK23059-3. 2 records from A new western Canadian record of Epeoloides pilosulus (Cresson), with discussion of ecological associations, distribution and conservation status in Canada. 3 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 1 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 1 records from Colección Ornitológica del Museo de Historia Natural de la Universidad de la Amazonia. 85 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 18 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 36 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 242 records from Landschaftspflegehof (Berlin). 1553 records from University of Valencia cetacean surveys in the Spanish Mediterranean 2000-2003. 10 records from Bachpatenschaft Beeke. 5300 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 51 records from Total foraminifera counts from M35/1_MSN1051. 341 records from SPC CoFish Invertebrates Observations Niue 2005. 7 records from Illustrated identification key to the genera of New World Micrelytrini (Hemiptera: Alydidae: Micrelytrinae), with description of two new genera, one new species and new distributional records. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 195 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 74 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 160 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 167 records from Artenvielfalt auf den Elbwiesen (Dessau). 863 records from Données naturalistes de Daniel PAVON. 14 records from Modelaje de la distribución potencial de 10 especies de anfibios y reptiles en riesgo de extinción con escasos registros de presencia (ANONAU). 707 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 59 records from Seabird and cetacean sightings from Cruise SY002 of RV Shoyo Maru, Tropical Atlantic Ocean, Oct. 2000. 98 records from A revision of the minor species group in the millipede genus Nannaria Chamberlin, 1918 (Diplopoda, Polydesmida, Xystodesmidae). 201 records from Total foraminifera counts of multinet M21/1_MSN606. 2045 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 16 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 122361 records from Estonian Nature Observations Database. 1 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 6 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 10 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 2 records from Genome sequencing reveals extraordinary cephalic horns in the Madagascan dung beetle genus Helictopleurus (Coleoptera, Scarabaeinae): insight from a revision of fungicola species group. 2 records from Description of three new velvet geckos (Diplodactylidae: Oedura) from inland eastern Australia, and redescription of Oedura monilis De Vis. 29916 records from Botanical Museum, Copenhagen, Mycology Herbarium. 4555 records from NCSM Mammalogy Collection. 798 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 8 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 91 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 797 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 48838 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 2 records from New Vietnamese Species Of The Genus Flavoperla Chu (Plecoptera: Perlidae). 67699 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 2 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 2 records from Planktic foraminifera counts of multinet PS2616-5. 16 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2445-2. 4207 records from CASES2003_2004. 359 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Xiloteca). 18771 records from Fife Nature Records Centre combined dataset. 3 records from CHAS Botany Collection (Arctos). 203 records from Total foraminifera counts of multinet M21/1_MSN604. 4 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 4 records from Leuctra Pinhoti, A New Species Of Stonefly (Plecoptera: Leuctridae) From Alabama, U. S. A.. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 1 records from Bryoerythrophyllum subcaespitosum (Pottiaceae), a new combination for a neglected species from South America. 14 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 31 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 3092 records from Odonata de Veracruz. 85 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 2 records from Revisions to the faunas of Andrena of the Iberian Peninsula and Morocco with the descriptions of four new species (Hymenoptera: Andrenidae). 312 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 65 records from A review of the genus Cyana Walker, 1854 from India, with descriptions of five new species and three new subspecies (Lepidoptera: Erebidae: Arctiinae: Lithosiini). 83 records from (Table 6) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-849B. 925 records from Mushrooms Flora of Nepal at National Herbarium and Plant Laboratories (KATH). 5 records from Two new species of Tipula (Vestiplex) Bezzi (Diptera, Tipulidae) from Northwest China. 235 records from Chronicle of Nature - Phenology of Birds of Ilmensky State Nature Reserve, Russian Academy of Sciences, Urals Branch. 10 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 3586 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 2 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 2 records from Descriptions of two new shell-dwelling species of Metriaclima (Cichlidae) from Lake Malaŵi, Africa. 1379 records from Composition of the coccolith flora in sediment core GeoB1710-3. 185 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 3 records from Collection Ephemeroptera - SMF. 68 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 146 (N.S) n° 39 (1), 2011 - Données faune. 44 records from Microzooplankton abundance and biomass at station TT045_15-2. 5677 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 10461 records from Denver Museum of Nature & Science - Entomology. 1 records from A new species of Athaumasta Hampson, 1906 (Lepidoptera, Noctuidae, Bryophilinae) from the Altai Mountains of Mongolia and China. 42 records from (Table 1) Abundance, wet biomass, and carbon biomass of all major groups of phytoplankton in the water column of the Kara Sea. 8735 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 506 records from Database for alien invasive plants occurrences in Germany. 9 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 6 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 1215 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 364 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 62 records from Benthic foraminifera abundance of Hole 84-566C. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 115 records from Strathclyde badger sett surveys 1996-2000. 454 records from (Appendix B) Relative abundances of larger size planktonic foraminifera in latest Maastrichtian sediments of DSDP Hole 74-525A from Walvis Ridge, South Atlantic. 871 records from SEFSC Southeast Cetacean Aerial Survey 1992. 14679 records from Abundance of Rocky Reef Fishes, Invertebrates and Algae, Reef Check California (RCCA), 2006 - 2017. 495 records from OUPR - Herbário "Professor José Badini". 4 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 34928 records from National Biodiversity Data Bank. Observation records, 1900-2014. 284 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 6 records from 20th century Betula pubescens ssp. czerepanovii tree- and forest lines in Norway. 56 records from Total foraminifera counts of multinet M21/4_MSN720. 9752 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 7483 records from Larvae of decapods off Portuguese coast from 1986 to 1994. 104 records from Range table from benthic foraminifers in ODP Hole 172-1059B. 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 92 records from Nottekanal, Klasse 7 - 10. 27 records from A new Phoberus MacLeay species (Coleoptera: Scarabaeoidea: Trogidae) from the Maloti-Drakensberg Mountains of southern Africa and the Phoberus caffer species group reviewed. 4 records from Amoeboid protists isolated from ancient Siberian permafrost. 1821 records from Inventaire des Mollusques Sphaeriidae de France. 269 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_93MC. 66054 records from Finnish Floristic Database (Literature Sources). 9 records from Analyses of the recent components in the sand fraction of sediment core PS1278-1. 1053 records from (Table 14) Calcareous nannofossil occurrences in ODP Hole 130-806B. 1 records from A new species of Nasusina Pearsall from Colorado (Lepidoptera: Geometridae: Eupitheciini). 46077 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 1719 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 4 records from Microplankton counts and carbon biomass at station TT011_4-CTD46. 3 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 326622 records from iNaturalist Research-grade Observations. 143 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 2 records from Two new species of the genus Cataglyphis Foerster, 1850 (Hymenoptera: Formicidae) from Iran.. 14 records from Bohemannia auriciliella (Nepticulidae) specimen data. 1365 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 1 records from A contribution to the knowledge of the prominent moths (Lepidoptera, Noctuoidea Notodontidae) of the Maputo Special Reserve with descriptions of four new species. 13 records from Synopsis of world Discleroderma Kieffer (Hymenoptera, Bethylidae). 201 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 212 records from Planktic foraminifera abundance of Hole 84-567A. 1 records from Cladistic analysis and synopsis of Chloropepla Stål (Hemiptera: Heteroptera: Pentatomidae) with the description of three new species. 1242 records from Range table from planktonic foraminifers in ODP Hole 159-960C. 22 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 4105 records from DBG Mirabilis rotundifolia Demographic Monitoring. 2 records from Range table from planktonic foraminifers in ODP Hole 178-1102C. 32 records from (Appendix F) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749C. 24 records from Abundance of benthos infauna at station PS1240-1. 1113 records from Marine algal flora of Flores and Corvo Islands, Azores. 1079 records from Mediterranean seabird surveys 99/00/02. 110 records from Données du Râle gris sur le territoire de la Guadeloupe. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 27 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 12 records from Microzooplankton abundance and biomass at station NBP97-03-12-2. 18 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5120-2. 419 records from données arachnologiques de CARR David. 2 records from A new species of the genus Verilus (Teleostei, Percomorpha, Acropomatidae) from Brazil. 140 records from (Table 2) Distribution of selected planktonic foraminifer species at ODP Site 124-770. 2619 records from HUEFS herbarium - Universidade Estadual de Feira de Santana - Herbário Virtual REFLORA. 4725 records from (Table 7) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-709C. 5 records from Two new species of Carcinoplax H. Milne Edwards, 1852, and Pycnoplax Castro, 2007, from the western Pacific, and a description of the female of Thyraplax truncata Castro, 2007 (Crustacea, Decapoda, Brachyura, Goneplacidae). 7 records from Planktic foraminifera abundance of Hole 94-611B. 1403 records from Relative abundance of planktic foraminifera in sediment core GeoB1312-2. 2 records from Description of two new species of Regalana and a new genus of Gyponini (Hemiptera: Cicadellidade: Iassinae). 2 records from Taxonomic study of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) VIII. The densimacularis species group, with descriptions of four new species. 2 records from Microzooplankton abundance and biomass at station TT054_24-22. 3 records from New records of the water mite genus Arrenurus Dugès, 1834 from South America (Acari: Hydrachnidia: Arrenuridae), with the description of five new species and one new subspecies. 2143 records from Range table from benthic foraminifers in ODP Hole 154-929A. 112 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 142 records from Données du naturaliste Arnaud Bak. 57219 records from Derek Lott Coleoptera Dataset. 11508 records from JCT AVH data. 12339 records from University of Tennessee Bryophyte Herbarium. 1279 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 451 records from PINK - Dragonfly (Odonata) monitoring for the permanent surveillance of coastal areas in Flanders, Belgium. 3018 records from Likona Invertebrates. 73 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 22 records from Exceptional diversity of Tischeriidae (Lepidoptera) from a single tropical forest site in Belize, Central America. 128102 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 339 records from Amphibiens de Guyane. 8563 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 4 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 29 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5112-4. 575 records from Nannofossil abundance of Hole 75-530A. 1 records from Happywhale - Fin Whale in South Atlantic Ocean. 102 records from Acoustic detections from research cruises in the Med sea, 1994-2001. 4591 records from DBRC Hemiptera species records 1969 to 2015. 448 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 63883 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 1035 records from (Table 9) Benthic foraminifera in early-middle Miocene sediments of DSDP Hole 90-591B. 4 records from Revision der Gattung Agachila D & G - M, 1954 (Hemiptera: Heteroptera: Tingidae). 699 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-908A. 25 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 2662 records from Dorset SW Pilot species dataset. 43 records from Contrasting species diversification of Eutarsopolipus (Acariformes: Podapolipidae) on Castelnaudia and Notonomus (Coleoptera: Carabidae). 1911 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 9 records from Benthic macrofauna abundance of sediment core 13077-087. 96 records from (Table 2e) Nannofossil distribution chart of petroleum well Leeuwin-1. 383 records from MCCC - Mendocino College Coast Center Herbarium. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 992 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 4751 records from Cumbria Non Native Invasive Species. 459 records from Lower Albian l'Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 176 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 1667 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2007. 317 records from Benthic foraminifera and algae abundance of Hole 81-554A. 982 records from Diatom assamblage in samples from sediment trap OG4. 266 records from DAR AVH data. 117877 records from England Non Native Species records 1965 to 2017. 1 records from Studies in Australian Tettigoniidae: New Fully-winged Agraeciini From Northeastern Australia (Orthoptera: Tettigoniidae; Conocephalinae; Agraeciini). 349 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 16 records from Abundance and carbon biomass of phytoplankton at station TT007_4-CTD48. 16 records from Review of the Orphninae (Coleoptera: Scarabaeidae) of Sri Lanka, with description of a new species of genus Orphnus Macleay, 1819. 41 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 8 records from Microzooplankton abundance and biomass at station TT050_17-4. 7 records from New taxa and new records of Deltocephalini leafhoppers from Thailand (Hemiptera: Cicadellidae: Deltocephalinae). 65 records from DBL_Life. 240 records from Colección Ornitológica de la Universidad Tecnológica del Chocó. 1014 records from Océanopolis mammifères marins en Bretagne 1993-2015. 5 records from Studies of the genus Anthelephila Hope (Coleoptera: Anthicidae). Part 19. New species from Indonesia and Malaysia. 15658 records from BLS Rare and Threatened Lichen Records: England. 16 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 1 records from Gronau - auf der Suche nach dem Neunauge. 77 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México (Tamaulipas). 141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 78 records from (Table 4) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-599. 1 records from Discovery of the transantarctic distribution of the genus Metanteon Olmi (Hymenoptera: Dryinidae), with description of a new species from New Caledonia. 1028 records from Nannofossil abundance of Hole 94-607. 12 records from Description of two new species of Sindosium Johnson, 2007 from Australia (Coleoptera, Ptiliidae). 1664 records from Thrips (Thysanoptera) in Norway. 69 records from Entdeckertour am Muldestausee 1/05. 765 records from Abundance and distribution of coastal, inshore zooplankton in the Huon Estuary and D'Entrecasteaux Channel, Tasmania, Australia (2004-2005). 69 records from BID-Malawi-Arctiidae-Biodiversity-Data. 372 records from Chronicle of Nature - Phenology of Plants of State Environmental Institution National Park Braslav lakes. 2007 records from Demersal and pelagic species of fish and squid from the Patagonian shelf. 2 records from Description of a new diminutive, rupicolous species of day-gecko (Squamata: Gekkonidae: Cnemaspis) from southern Sri Lanka. 1098 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 1345 records from Weevils of Poland. 4 records from New records of eumenine wasps (Hymenoptera: Vespidae: Eumeninae) from Russia with description of a new species of Leptochilus de Saussure, 1853. 4 records from A new genus and species of Stigmoderini Lacordaire, 1857 (Coleoptera: Buprestidae: Buprestinae) from Southeast Brazil with notes on its hypothesized mimicry complex. 1652 records from Arachnida of Costa Rica (INBio). 6 records from New and confirmed records of fruit flies (Diptera, Tephritidae) from Italy. 23 records from Données du naturaliste RADOGEWSKI Alain provenant de la base de donnée du SINP Île-de-France CETTIA. 8 records from Benthic macrofauna abundance of sediment core 13078-015. 568 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 1297 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 917 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 10075 records from Nematoda of Costa Rica (INBio). 1 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 1 records from Revision of the family Acidopsidae Števčić, 2005, and the systematic position of Typhlocarcinodes Alcock, 1900, Caecopilumnus Borradaile, 1902, and Raoulia Ng, 1987, with descriptions of two new genera and five new species (Crustacea: Brachyura: Goneplacoidea). 18579 records from WTSWW Data: All Taxa (West Wales). 4 records from Two more new species of the Cyrtodactylus peguensis group (Squamata: Gekkonidae) from the fringes of the Ayeyarwady Basin, Myanmar. 38 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 412254 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 162299 records from South Australian Museum Australia provider for OZCAM. 75 records from New species and records of Caulleriella (Annelida, Cirratulidae) from shelf and slope depths of the Western North Atlantic Ocean. 31 records from Plasm bearing foraminifera counts from multinet M32/3_MSN957. 3 records from Coccolith counts of multinet M32/5_MSN981. 6 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 15 records from Brock University Herbarium (BU). 160 records from (Table 1) Distribution of planktonic foraminifers in ODP Hole 126-787B. 117 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1246-4. 7115 records from Whicher Scarp Flora Survey. 16 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 2269 records from UNCW Marine Mammal Aerial Surveys 2006-2007. 2 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 50 records from New species and records of deep-water Orbiniidae (Annelida, Polychaeta) from the Eastern Pacific continental slope, abyssal Pacific Ocean, and the South China Sea. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 110 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 278 records from Gomex Sperm Whale Survey 2000. 2 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 1092 records from Modernisation des ZNIEFF du PnrL. 4 records from The West and Central African species of Vepris Comm. ex A. Juss. (Rutaceae) with simple or unifoliolate leaves, including two new combinations. 2 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 21 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 14 records from UWIZM Cnidarians. 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 11 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 90756 records from Tasmanian Museum and Art Gallery provider for OZCAM. 21 records from TTRS Mammals. 1794 records from (Table 13) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-715A. 3249 records from Benthos counted on dredged samples during Valdivia cruise VA53. 1 records from The genus Semicerura (Collembola; Isotomidae) in Asia. 5170 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 44 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 214 records from Total foraminifera counts of multinet M21/1_MSN608. 19 records from A new species of the genus Tetragonopterus Cuvier, 1816 (Ostariophysi: Characiformes: Characidae) from the rio Tocantins drainage, Brazil. 606 records from Carabidae of the European North-East of Russia. 3085 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 1202 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 2 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 4038 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 262 records from Variability of benthic Foraminifera north and south of the Denmark Strait. 1 records from The genus Chionanthus (Oleaceae) in Cambodia, Laos and Vietnam. 12 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD63. 862 records from Palynological analysis of sediment core GeoB9508-5. 3 records from Novel taxa of Cheilostomata Bryozoa discovered in the historical backlogs of the Iziko South African Museum. 21 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 6 records from Abundance of benthos infauna at station GIK23065-1. 13422 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 1 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 283 records from Flux data of NU2_trap (Table A1). 2413 records from Arachnids (Aranei, Opiliones) from grass stand and forest litter in the Urals, Russia. 2000783 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 15 records from Capobula gen. nov., a new Afrotropical dark sac spider genus related to Orthobula Simon, 1897 (Araneae: Trachelidae). 14 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 5 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 27 records from Bishop's University Insect Collection (BUIC). 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 125443 records from BioFokus. 47 records from Anymals+plants - Citizen Science Data. 830 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 41 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 1 records from Happywhale - Blue Whale in Southern Ocean. 3525 records from Happywhale - Humpback Whale in North Atlantic Ocean. 1865 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 473 records from CNAN/Scorpiones. 94 records from Total foraminifera counts of multinet M26/1_MSN845. 39 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 63-125 µm fraction. 2 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 400 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 2 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 2064 records from Ross A. Layberry, Collection. 30 records from Occurrence of some antimalarial plants from Cameroon. 14 records from New gnathiid isopod crustaceans (Cymothoida) from Heron Island and Wistari Reef, southern Great Barrier Reef. 13 records from Royal Belgian Institute of Natural Sciences marine Chelicerata collection. 74 records from Birdrace_Gätkes_Schergen-Helgoland. 668 records from (Table 12) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A. 197 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/092-6. 4 records from Microplankton abundance at bottle station SEPT-1999-K7. 5 records from New records of Munidopsis (Crustacea: Anomura: Galatheidae) from New Zealand with description of two new species from a seamount and underwater canyon. 7 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 234 records from Pollen analysis of sediment profile BLA00 from Blankensee. 1 records from DRYMONIA MEXICANA (GESNERIACEAE), A NEW ENDEMIC SPECIES FROM VERACRUZ (MEXICO) Laura Clavijo. 7129 records from NCSM Non-molluscan Invertebrates Collection. 80 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM3. 301 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto29-38. 97042 records from The AAU Herbarium Database. 194 records from Sistematización de la Colección Entomológica Forestal del CENID-COMEF. 18 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 751 records from Colecção Entomológica do Museu de História Natural de Maputo. 188 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 24 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 324 records from Chronicle of Nature - Phenology of Birds of Volzhsko-Kamsky National Nature Biosphere Rezerve. 8 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-10. 18 records from Craigellachie NNR invertebrate records compiled from SNH files. 240 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 6 records from Hydrographic profiles in South West Atlantic Ocean derived from Southern Elephant seals dives. 102 records from Collection Polychaeta - ZSRO. 2247 records from imr_mareano_rpsledge. 1 records from Données du/de la naturaliste LUPOLI ROLAND provenant de la base de donnée du SINP Île-de-France CETTIA. 200 records from Bats of Kim Hy Natural Reserve, Vietnam. 38783 records from Herbario de la Facultad de Ciencias Biológicas de la Universidad Complutense de Madrid (MACB). 2 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 796 records from (Table 2) Relative abundance of 13 species of planktonic foraminifers of sediment core GIK17938-2. 59 records from Cayman Islands 2004: Loggerhead & Green Turtles (aggregated per 1-degree cell). 675 records from (Table 5) Planktonic foraminifer abundance of ODP Hole 162-982A. 10 records from Revalidation and taxonomic revision of Teloneria Aczél (Diptera, Neriidae), with description of two new species. 6 records from Leptoclinides (Ascidiacea, Didemnidae) from Brazil: new records and two new species. 75 records from Range table from planktonic foraminifers in ODP Hole 170-1040B. 62 records from Total living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >30 µm. 10 records from Microzooplankton abundance and biomass at station TT050_7-9. 822 records from Coleoptera Collection. 118 records from BID-Malawi's-Notodontidae-Biodiversity-Data. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 618 records from Kangawalla Bird Sightings. 9 records from Michigan Plecoptera (Stoneflies): Distribution Patterns And An Updated Species List. 196 records from North Marine Region sawfish collection records (DEW collation), Australia (1912 - 2004). 5 records from Four new species and new records of Manota (Diptera: Mycetophilidae) from Sulawesi, Indonesia. 371 records from Planktic foraminifera and paleoclimate temperature and salinity calculations from sediment core M44/1 GeoTü KL71. 245 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hymenoptera (ZUFMS-HYM). 3 records from Description of five new species in the genus Phlyctinus Schoenherr (Coleoptera, Curculionidae): a first step in deciphering the P. callosus complex. 1 records from Description of a new species of Ochraethes Chevrolat, 1860, redescription of Plocaederus mirim Martins and Monné, 2002, and new geographical records for Plocaederus Dejean, 1835 (Coleoptera, Cerambycidae, Cerambycinae). 5045 records from The Fungal, Lichen and Plant Collections at the Herbarium Marburgense. 16 records from Chronicle of Nature - Phenology of Mushrooms of FGBU National Park Kenozersky. 10261 records from Florida Manatee Synoptic Aerial Survey 1991-2019. 84 records from DREAL_PACA_-_N2000_-_Naturalia_2017_12_18. 1 records from Discovery of a new species of Embolemus Westwood (Hymenoptera: Embolemidae) from New Caledonia. 831 records from “Phytoplankton and Zooplankton data collected during the Black Sea cruises of UkrSCES R/V "Georgyi Ushakov" in 1992”. 436157 records from Welsh Invertebrate Database (WID). 14 records from Lauchhamer GEO-Tag der Artenvielfalt. 2653 records from Bulletin mensuel de la société linnéenne de Lyon [1932- ]. 671 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part II. 3 records from Four New Bat Species (Rhinolophus hildebrandtii Complex) Reflect Plio-Pleistocene Divergence of Dwarfs and Giants across an Afromontane Archipelago. 3683 records from Dipterists Forum - Recording Scheme - Stilt & Stalk Flies. 1 records from First Australian records of Ethusina (Crustacea: Decapoda: Ethusidae) and additional records from New Zealand. 18315 records from Abundances and biological traits of the juveniles salmon sampled in the survey of Salmon abundance Indices in the Scorff river (France). 4 records from Miscophus Jurine, 1807 (Hymenoptera, Crabronidae) in Central, Northern, and Eastern Europe. 1116 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 3. 2 records from Microzooplankton abundance and biomass at station TT054_21-15. 16 records from Lannapsyche and Marilia species of China (Trichoptera: Odontoceridae). 7762 records from Données naturalistes de Pierre FRAPA. 360 records from (Table 2) Distribution of silicoflagellates, actiniscidians, and ebridians in selected samples from ODP Hole 112-683A. 9 records from Range table from planktonic foraminifers in ODP Hole 169-1038H. 5 records from Description of two females of Leptagrion Selys (Odonata: Coenagrionidae). 1 records from Redescription of Inglisia vitrea Cockerell (Hemiptera, Coccidae) and its transfer to the genus Pseudokermes Cockerell. 228 records from Biodiversidad acuática del río Amacuzac, Morelos, México (Plantas Acuaticas Río Amacuzac). 34 records from Données de l'enquête Escargots de l'ONEM (onem-france.org). 1144 records from Lapwing Recovery Project, South West Scotland, 2006-2009. 44 records from Antarctic Euphausiacea occurrence data from ITALICA 2000 Expedition. 3 records from Neotropical spittlebugs related to Neaenini (Hemiptera, Cercopidae) and the origins of subfamily Cercopinae. 118 records from Natur aus zweiter Hand am Muldestausee. 169 records from Microzooplankton abundance measured on water bottle samples at station PS58/038-3. 198084 records from Limnic freshwater benthic invertebrates biogeographical mapping/inventory NTNU University Museum. 25 records from Vermont Records of Crayfish Worms (Branchiobdellidans) and Associated Crayfish Hosts. 5 records from Philinidae, Laonidae and Philinorbidae (Gastropoda: Cephalaspidea: Philinoidea) from the northeastern Pacific Ocean and the Beaufort Sea (Arctic Ocean). 4848 records from Mamíferos de los Parques Nacionales Lagunas de Montebello y Palenque, Chiapas. 1 records from Cardiocondyla atalanta Forel, 1915, a cryptic sister species of Cardiocondyla nuda (Mayr, 1866) (Hymenoptera: Formicidae).. 50044 records from NHMO DNA Bank Vascular plants collection. 841 records from HPL - Herbário do Jardim Botânico Plantarum. 35 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/045-2. 120 records from (Figure 2) Distribution of dinoflagellate cysts in the mid-Cretaceous of ODP Hole 101-627B. 3498 records from Observations et collection de Coléoptères d'Alain Sadorge. 2 records from Hidden diversity within the Nemastoma bidentatum Roewer, 1914 complex (Opiliones: Nemastomatidae) Part I: Morphological evidence. 25 records from Total foraminifera counts of multinet M42/3_MSN1368. 2 records from Notes on the spider genus Segestria Latreille, 1804 (Araneae: Segestriidae) in the East Palaearctic with description of three new species. 2838 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1995-1999. Part 1. 83204 records from Marine data from Natural Resources Wales (NRW) Technical Support (Research & Monitoring) Contracts, Wales. 19 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, >125 µm fraction. 313 records from Stadtpark Herzberg (Elster). 78 records from TTRS Ornithology. 13 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 131 records from Unser Schulhof - eine Apotheke. 691 records from Black grouse national surveys. 20 records from B herbarium - Botanischer Garten und Botanisches Museum Berlin-Dahlem Herbarium - Herbário Virtual REFLORA. 1234 records from Southern Maine Community College Gulf of Maine Invertebrate Data. 4 records from On Sahastata (Araneae: Filistatidae): complementary description of the generotype and two new species from Oman and Morocco. 37 records from Berlin - Treptower Park / Karpfenteich. 596 records from El género Bursera en México. Parte II. 4852 records from HUFU herbarium - Universidade Federal de Uberlândia - Herbário Virtual REFLORA. 66 records from Lord Fairfax Community College Herbarium. 17 records from Dinoflagellate cysts of sediment core IOW211630-9. 307 records from PSUZC-Mammal Collection. 23 records from Canadian National Collection of Insects. 1 records from The Cephenniini of China. IX. Cephennomicrus Reitter of Yunnan (Coleoptera: Staphylinidae: Scydmaeninae). 264 records from (Appendix 5) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2039. 8721 records from Actualisation de la cartographie des Ptéridophytes de France et d'Europe occidentale. 516 records from (Table 6) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1018A sediments. 87 records from Gulf of Gdansk. 806 records from Planktic foraminifera abundance of Hole 80-549A. 9591 records from Museu Paraense Emílio Goeldi - Diptera Collection. 704 records from NEFSC Aerial Survey - Summer 1998. 424 records from Coleção de Ictiologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZIUMCN-UNIVATES). 1170 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 188 records from Feeding rhythms of the common goby Pomatoschistus microps at the brackish tidal marsh 'Het verdronken land van Saeftinge' in 1994. 13187 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 294 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE275. 1143 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2000. 768 records from (Figure 8c) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-536. 53 records from Phytoplankton abundance at station Sechin_2003-12-28_1, Casma, Peru. 17092 records from Herbarium Senckenbergianum (FR). 2919 records from Invertebrate Zoology Division, Yale Peabody Museum. 1 records from DREAL Auvergne - Reptiles - 2015. 9 records from Six new species of Stenometopiini (Hemiptera: Cicadellidae: Deltocephalinae) with redescription of additional species and new distributional records. 334 records from Merseyside BioBank Active Naturalists (unverified). 6738 records from Regeneración de especies arbóreas del bosque mesófilo en las montañas del norte de Chiapas. 31 records from New Species And New Records Of Plecoptera From Korea And The Russian Far East. 119 records from (Table 1) Distribution of Cretaceous redeposited benthic foraminifers at DSDP Hole 89-585. 168 records from Sea trout entering the rivers Adour and Nivelle in south-west France at the start of the 21st century. 4 records from Nymphs of some Nearctic leafhoppers (Homoptera, Cicadellidae) with description of a new tribe. 54176 records from CHSC - CSU Chico, Chico State Herbarium - Vascular Plants. 1054 records from Mound building termites contribute to savanna vegetation heterogeneity- woody plants, forbs and graminoids. 31418 records from Swiss National Vespoidea Databank. 20 records from CHAS Ichthyology Collection (Arctos). 45 records from Planktic foraminifera abundance of Hole 73-520. 621 records from “Phytoplankton and Zooplankton data collected during the Black Sea cruises of UkrSCES R/V "Ernst Krenkel" in 1992”. 1517 records from (Table 4) Distribution of planktonic foraminifers in ODP Site 126-792. 428441 records from Israel Nature and Parks Authority. 55 records from Range table from benthic foraminifers in ODP Hole 171-1052A. 10 records from New Species And Records Of Asian Peltoperlidae (Insecta: Plecoptera). 19 records from Colección de muestras biológicas del Centro Oceanográfico de Canarias. 10 records from NMML Harbor Porpoise Aerial Survey, Bristol Bay, Replicate 2, 1991. 5611 records from Micro-moths distribution for Dumfries and Galloway. 27 records from Liogenys Guérin-Méneville, 1831 (Coleoptera: Scarabaeidae: Melolonthinae) from the southern South American Transition Zone and boundaries: taxonomic overview with four new species. 1236 records from Données araignées de JACQUET Claire. 1196 records from Biodiversidad de moluscos opistobranquios (Mollusca: Opisthobranchiata), del Pacífico mexicano: Isla Cedros-Vizcaíno. 555 records from NEFSC Aerial Survey - Experimental 2002. 194 records from Pottundkopp. 84 records from Recovery of the medicinal leech Hirudo medicinalis in Scotland - Phase II. 1 records from New species of Crella (Pytheas) Topsent, 1890 and Crellomima Rezvoi, 1925 (Crellidae, Poecilosclerida, Demospongiae) from Chilean shallow and Argentinean deep waters, with a synthesis on the known phylogenetic relationships of crellid sponges. 6271 records from Catálogo de insectos de la colección del Centro de Entomología. 871 records from Colección de Mamíferos (Mammalia) del Museo de Historia Natural de la Universidad de Caldas, Colombia. 38602 records from Fairchild Tropical Botanic Garden (FTG). 1 records from Species of Horismenus Walker (Hymenoptera: Eulophidae) associated with bruchid beetles (Coleoptera: Chrysomelidae: Bruchinae), including five new species. 1456 records from Diversidad de los mamíferos de la Reserva de la biósfera Tehuacán-Cuicatlán, Puebla-Oaxaca, México. 1247 records from Antarctic Jellyfish. 18 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1368. 262312 records from National Trust Species Records. 111805 records from Australian National Wildlife Collection provider for OZCAM. 280 records from Diversité floristique des espèces menacées prioritaires du Bénin (Afrique de l'Ouest).. 15910 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (Collembola). 1617 records from HUSC - Herbário Unisanta. 6540 records from Crispin S. Guppy Collection. 112 records from Copepoda associated with Caribbean reef-dwelling cnidarians, echinoderms and sponges. 950 records from NHM, Heteroptera. 629 records from Algae, Norwegian College of Fishery Science. 2 records from Alloscorpiops citadelle sp. n. from Thailand (Scorpiones: Euscorpiidae: Scorpiopinae). 34 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 96 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1372. 1 records from Revision of the subgenus Stigmatodipogon Ishikawa of the genus Dipogon Fox (Hymenoptera: Pompilidae: Pepsinae). 1 records from Two new Chinese species of Tomocerus at different stages of troglomorphic adaptation (Collembola, Tomoceridae). 628077 records from Australian Museum provider for OZCAM. 109 records from Revision of the South African endemic bee genus Redivivoides Michener, 1981 (Hymenoptera: Apoidea: Melittidae). 1 records from 5. Wiener Gemeindebezirk. 2062906 records from Observation.org, Nature data from around the World. 14 records from Données d'oiseaux. 82 records from Phytoplankton samples - 2001/02 V3 CLIVAR. 4 records from On the genus Hirsutopes Pajni, 1990, (Coleoptera: Curculionidae, Entiminae), with the description of a new species. 8 records from Black fungus gnats (Diptera: Sciaridae) of Queensland, Australia. Part I. Genera Chaetosciara Frey, Corynoptera Winnertz, Cratyna Winnertz, Epidapus Haliday, Keilbachia Mohrig, Lobosciara Steffan, Phytosciara Frey and Scatopsciara Edwards. 108 records from Biological data measured on water bottle sampels at station AT_II-119/5_35-4. 3029 records from Mammal records for Dumfries and Galloway. 1 records from Characidium chancoense, a new species of South American darter from the Río Cauca drainage, Colombia (Characiformes: Crenuchidae). 22 records from Range table from planktonic foraminifers in ODP Hole 143-865A. 99 records from osac_oarisma. 66667 records from Vascular plant herbarium, UiT Tromsø Museum. 189 records from Inventaire des Scléractiniaires de la région du Diahot (RAP). 58 records from Range table from benthic foraminifers in ODP Hole 181-1121B. 104 records from Rainforest and cloud forest Scolytodes (Curculionidae, Scolytinae, Hexacolini) from the Arthropods of La Selva inventory in Costa Rica: new species, new synonymy, new records. 21 records from Riedkanal Bötzingen. 58 records from Données du/de la naturaliste Williamson Thomas provenant de la base de donnée du SINP Île-de-France CETTIA. 5 records from Seven new species and additional records of Palaearctic Leptusa, primarily from Yunnan, China (Coleoptera: Staphylinidae: Aleocharinae). 387 records from Oceanic Society's Marine Mammal Sightings in Belize 1992 - 2011. 66 records from Invasive alien species Noccaea caerulescens (J. Presl & C. Presl) F. K. Mey. in the Republic of Karelia. 6 records from Revision Of The Australian Coccinellidae (Coleoptera). Genus Novius Mulsant Of Tribe Noviini. 1 records from Distribution of Aureoboletus projectellus in Europe. 4 records from (Table T10) Calcareous nannofossil stratigraphy of ODP Hole 198-1212A. 18356 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) planctónicas más frecuentes en el Golfo de California. 767536 records from Dragonfly records from the British Dragonfly Society Recording Scheme. 2 records from A new species of Hypsohapsis (Heteroptera: Schizopteridae: Hypselosomatinae) from the Brazilian Amazon. 16 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_276-1. 4 records from Colección de macroalgas de la costa Argentina (IADO-UNS-CONICET). 6256 records from Invasive Plant Atlas of the MidSouth (IPAMS). 4 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 35 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/091-4. 12 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 2 records from A Catalogue and Historical Study of the Odonata of Ecuador. 136 records from Planktic foraminifera abundance of Hole 94-610. 892 records from Biodiversity of the Desna river valley and its tributaries. 137 records from Códigos de barras de la vida en peces y zooplancton de México. 34719 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR50. 25 records from (Table 5) Abundance of selected helicoliths at DSDP Site 82-563 in the North Atlantic. 1 records from Two new species of Dentilabus Heinrich (Hymenoptera: Ichneumonidae: Ichneumoninae) from Japan and Korea, with redefinition of the genus. 1718 records from Fish of the Recherche Archipelago , Western Australia (2002). 5 records from Loricifera - SMF. 32 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 457614 records from KTP Ring Data. 1 records from Two new species of Darnini (Hemiptera: Membracidae) from Colombia and Peru. 64 records from Revision of the spider genus Mystaria Simon, 1895 (Araneae: Thomisidae) and the description of a new genus from the Afrotropical region. 1 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 7976 records from Arbeitsgemeinschaft Heuschrecken Österreichs. 4 records from Subspecies of Pleurota bicostella (Clerck, 1759) revisited and descriptions of nine new species in the P. bicostella species group (Lepidoptera: Gelechioidea Oecophoridae: Pleurotinae). 462 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 23 records from Morphologische Daten von Natrix. 1011 records from (Table 3) Ranges of benthic foraminifers from the late Eocene through the Oligocene in ODP Hole 115-707A. 180 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 15 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 6 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 38279 records from Happywhale - Humpback Whale in North Pacific Ocean. 101 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 290 records from CNAC/Coleccion Nacional de Acaros. 1214 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 352 records from hauterivian_echinoids_of_the_paris_basin. 229 records from Distribución y estructura poblacional de la tortuga de Berlandier, (Gopherus [=Xerobates] berlandieri) en México. 21 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_3-CTD4. 48 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1197. 31 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 243 records from Range table from planktonic foraminifers in ODP Hole 171-1052E. 7 records from Freshwater fish records via iRecord - additional species. 61 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1194. 20 records from Abundance of benthos infauna at station GIK23055-1. 3 records from Three new species of Tridentella Richardson, 1905 (Isopoda: Cymothoida: Tridentellidae) from New Caledonia. 84 records from Calcareous dinoflagellate cysts of multicorer M51/3_562-5, grain fraction < 20µm. 4 records from A new species of Anchoviella Fowler, 1911 (Clupeiformes: Engraulidae) from the Amazon basin, Brazil. 6 records from Benthic macrofauna abundance of sediment core 13200-017. 356 records from Ixias butterfly specimens at Museum Zoologi Bogor, Indonesia. 2 records from SJRP-Fungi - Herbário de fungos de São José do Rio Preto. 61 records from Riodinid butterfly specimens at Museum Zoologi Bogor, Indonesia. 1 records from Synonymies, a new combination, and four new species in Amphicnaeia Bates (Coleoptera: Cerambycidae: Lamiinae). 1180 records from Gunma Museum of Natural History, Fungi Specimen. 45 records from (Table 3) Distribution of late Cretaceous nannofossils in DSDP Hole 77-538A. 4544 records from Pteridophyte of the Urals and adjacent areas. 33 records from Range table from benthic foraminifera in ODP Hole 199-1215B. 28 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/061-3. 3 records from Two new genera and five new species of Tullbergiidae (Collembola) from the southern Appalachian Mountains of North America, with redescription of Tullbergia clavata Mills. 180 records from (Table 6) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides in DSDP Hole 79-545. 35 records from DUML vessel-based line transect surveys for proposed Onslow Bay USWTR site 2007-2010. 8 records from Qarshi Botanical Garden. 1620 records from (Table 2) Pleistocene nannofossil range chart for ODP Hole 134-828A. 4 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1335. 93871 records from PIROP Northwest Atlantic 1965-1992. 2 records from The oribatid mite genus Topalia in Australia (Oribatida: Nosybeidae) and the taxonomic status of related families and genera. 102 records from Organochlorine and total mercury in bivalve Anadara tuberculosa and other species from the Nicoya Gulf, Costa Rica in 1988. 21 records from Happywhale - Southern Right Whale in South Atlantic Ocean. 65 records from ZUEC-HEM - Coleção de Hemiptera do Museu de Zoologia da UNICAMP. 124499 records from UWFC Ichthyology Collection. 70 records from (Table 2) Occurrence of the most abundant nannofossil taxa in middle Cretaceous sediments of ODP Leg 129 sites. 1331 records from Mycological Collection of Osaka Museum of Natural History. 3728 records from Auburn University Museum of Natural History Invertebrates. 3575 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Queyras_2017_12_18. 2 records from Rhamphomyia Meigen of the Canadian Arctic Archipelago, Greenland and Iceland (Diptera: Empididae). 1 records from A new species of Novastoa Finlay, 1926 (Mollusca: Gastropoda: Vermetidae) from coral reefs of the Pacific Ocean. 11201 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 352 records from (Table 5) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-841A. 17 records from (Table 4a) Abundance of microalgae in surface layer bottom sediments at Station ST-RSh-1 in the northeast Black Sea. 307 records from Distribution of lithic fragments and the planktic foraminifera Neogloboquadrina pachyderma in quaternary sediments of DSDP Hole 94-609 (Table 2). 123465 records from NY herbarium - The New York Botanical Garden - Amostras Brasileiras Repatriadas - Herbário Virtual REFLORA. 407 records from (Table 4) Distribution of planktonic foraminifera in middle Miocene sediments of DSDP Hole 94-608 in the North Atlantic. 43 records from Vogelstimmenführung durch den Tiergarten. 448 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 1 records from The first blind spirostreptid millipede, found in a cave in Morocco; with notes on the genus Odontostreptus Attems, 1914 (Diplopoda, Spirostreptida, Spirostreptidae). 63 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1362. 11357 records from Inventaire des Ephémères de métropole (Opie). 293 records from Echinodermata of Montenegro (South Adriatic). 221 records from Tetrápodos de Uruguay. 25 records from Database of Arctic lamprey (Lethenteron camtschaticum (Tilesius, 1811)) occurrences in Russia and actual samples deposited in the A.N. Severtsov Institute of Ecology and Evolution.. 159 records from (Table 2) Range chart of benthic and planktonic foraminifera of ODP Site 127-794. 18 records from Sarcodine counts and carbon biomass at station TT012_5-TM28. 1 records from Phylogenetic analysis and systematic position of two new species of the ant genus Crematogaster (Hymenoptera, Formicidae) from Southeast Asia. 4959 records from Phenology and biological traits of adult migrating atlantic salmon (Salmo salar) sampled by trapping in the survey in the Nivelle river (France). 4464 records from Universidad de Barcelona (Facultad de Biología): Plantas vasculares del valle de Son del Pi y áreas colindantes. 34 records from Two new species of Petalophthalmus and Ipirophthalmus (Crustacea: Mysida: Petalophthalmidae), from New Zealand. 12 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 4 records from The Haliplidae (Coleoptera) of Atlantic Canada: new records, distribution, and faunal composition. 4251 records from University of Kentucky Insect Collection. 44566 records from Atlas des Orthoptères et Mantides de France métropolitaine. 23 records from Range table from planktonic foraminifers in ODP Hole 139-857B. 251 records from (Table 1) Ostracoda community from DSDP Hole 95-612. 667 records from Floodplain and aquatic vegetation survey, Okavango Panhandle, 2004. 3132 records from Resolute Passage Copepod Distribution (OBIS Canada). 13258 records from UAM Bird Collection (Arctos). 21 records from Twite, winter distribution in Caithness and Sutherland 2006/7. 2 records from A new species of Eremias (Squamata: Lacertidae) from the arid mountains of Pakistan. 2 records from Encyocratella olivacea Strand, 1907, a senior synonym of Xenodendrophila gabrieli Gallon, 2003 (Araneae: Theraphosidae: Stromatopelminae) with a description of the male. 307 records from UTEP Herpetology Osteology (Arctos). 2072 records from Vertical distribution of meiofauna in the North Sea and the Westerschelde estuary in 1993 and 1994. 20443 records from The Scottish Squirrel Database. 32 records from Pittosporum sucker (Trioza vitreoradiata) records aquired by the Royal Horticultural Society. 2 records from Taxonomy of Tabanus trivittatus species-group (Diptera: Tabanidae), with description of five new species. 46 records from Wood Stork Tracking (aggregated per 1-degree cell). 1 records from Acmaeodera (Ptychomus) kubani sp. n. from Northern Africa and the Arabian Peninsula, with notes on the taxonomic composition of the subgenus Ptychomus Marseul, 1866 (Coleoptera: Buprestidae: Polycestinae: Acmaeoderini). 36 records from Selz (Ingelheim am Rhein). 2647 records from SPC CoFish Fish Observations Nauru 2005. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 387 records from Distribución espacio-temporal de las larvas de atunes en el Golfo de Tehuantepec, México. 102 records from A Lichen Survey of the Ben Nevis Plateau. 1 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 974 records from Survey dataset on Pomatoschistus minutus (Pallas, 1770) and other gobies at the Belgian Coast, Oosterschelde, Westerschelde and at nuclear plants near Doel & Borssele. 1 records from Collection Crustacea - KAUMM. 2146 records from Benthos, zoo- and phytoplancton data collected during the monitoring cruise of RV "Vladimir Parshin" in 1996.. 235 records from FBIP: Baboon spider distribution records from selected South African museums. 52 records from Abundance of living benthic foraminifera in sediment core CD86_09_BC1. 207 records from Données du naturaliste Tillier Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 493 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/511-12. 13 records from Coccolith counts of multinet SO119_MSN1301. 2299 records from Colección de Oligoquetos Acuáticos de la UPV/EHU. 206 records from Review of the braconid parasitoid subfamily Doryctinae (Hymenoptera, Braconidae) from the United Arab Emirates and Yemen. 8 records from Three new species of squat lobsters of the genus Fennerogalathea Baba, 1988 (Decapoda: Galatheidae) from the Pacific Ocean. 20984 records from UWBM Mammalogy Collection (Arctos). 1026 records from Royal Ontario Museum Fungarium (TRTC). 255 records from El código de barras de las especies NOM-059 de mamíferos del Noroeste de México. 486 records from Butterfly_conservation_2017_12_18. 1 records from Inventaires faune. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 69037 records from Cranefly (Diptera; Tipuloidea) records for Britain to 2016. 8 records from Two new species of Crocodile Skinks (Squamata: Scincidae: Tribolonotus) from the Solomon Archipelago. 12053 records from Données bibliographiques et opportunistes Odonates issues du SIRF. 461 records from Benthic foraminifera counts of sediment core GIK23342-6. 99 records from Düne am Ulvenberg (Darmstadt). 5 records from Synopsis of the parasitoid wasp genus Cotesia Cameron, 1891 (Hymenoptera: Braconidae: Microgastrinae) in Australia, with the description of seven new species. 9136 records from Mammals housed at MHNG, Geneva. 25 records from Löydös Open Invasive Alien Species Observations. 330 records from Phytoplankton abundance measured on water bottle samples at station PS65/424-3. 136 records from Grillhütte Wettsaasen, Wiese, Hecken. 10 records from Sediment properties of core PLG95B_01BOXG. 1771 records from Swiss Psyllid (Hemiptera) Collections - Basel. 1 records from The genus Heteragrion (Odonata: Zygoptera) in Northwestern Colombia, with the description of Heteragrion tatama sp. nov.. 130 records from Plasm bearing foraminifera counts of multinet M21/1_MSN607. 257 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE206. 61 records from UWIZM Mantodea. 364 records from Distribución actual y potencial de veinte especies de hongos silvestres comestibles en los bosques de coníferas del estado de Oaxaca. 28 records from Microplankton counts and carbon biomass at station TT008_5-CTD61. 1 records from Validation of the status of a species with high CO 1 and low nuclear genetic divergences: the scab mite Caparinia ictonyctis stat. res. (Acariformes: Psoroptidae) parasitizing the African hedgehog Atelerix albiventris. 1 records from Taxonomic study of Hoplias microlepis (Günther, 1864), a trans-Andean species of trahiras (Ostariophysi: Characiformes: Erythrinidae). 249 records from Taxonomía y prospección del hábitat de las poblaciones de Bursera sect. Bullockia con especial énfasis en las especies afines al 'linaloe', B. aloexylon (Schiede ex Schlecht.) Engl.. 115 records from Mollusca specimens of Kuroshio Biological Research Foundation. 204 records from données bibliographiques diverses (non araignées). 4 records from Description of the female of the cellar spider Mesabolivar guapiara (Araneae, Pholcidae) from Mata Atlântica, Brazil. 4 records from Small, uniform, and rarely collected-an integrated taxonomic revision of Afromicracis bark beetles (Coleoptera, Scolytinae). 336 records from Phenological Center - Plants (Murmansk). 1 records from Four new species of Scaphochlamys (Zingiberaceae) from Peninsular Malaysia. 5074 records from SPC PROCFish/C Fish Observations Papua New Guinea 2006. 1518 records from (Appendix B) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-748B. 2 records from Taxonomy of Ecuadorian water beetles in the genus Hydrochus Leach, 1817 (Coleoptera: Hydrochidae). 25 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 722 records from Bird specimens of Komatsu City Museum. 83 records from Total foraminifera counts of multinet M21/5_MSN728. 6402 records from Macro- and megafauna from the North Aegean Sea from 1997-1998. 7 records from A survey of Phrurolithidae (Arachnida: Araneae) in southern Caucasus, Iran and Central Asia. 3 records from A new species of Paratelmatobius (Anura: Leptodactylidae: Paratelmatobiinae) from the Atlantic Forest of southern Brazil. 2 records from Description and life cycle of the hydrozoan Hydractinia uniformis, sp. nov. (Cnidaria: Hydrozoa: Hydractiniidae), from the coast of southeastern Brazil. 60 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 10 records from Three new species of the genus Neuquenaphis (Hemiptera, Aphididae, Spicaphidinae) from southernmost South America. 16 records from Collection Crustacea - ZSRO. 3965 records from SPC PROCFish/C Fish Observations French Polynesia 2003, 2004 and 2006. 1530 records from Digitalización de la Biblioteca de Sonidos Naturales del Museo de Zoología, Facultad de Ciencias, UNAM. 118 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México (Sinaloa_2008). 682 records from (Appendix B) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene sediments of DSDP Hole 94-610A from the North Atlantic. 1554 records from (Table 1) Relative abundance of planktonic foraminifers in ODP Hole 164-997A sediments. 91 records from Loup 2004 présence régulière communale (réseau Loup-Lynx ONCFS). 1365 records from Abundance and biomass of zooplankton collected in front of the Danube Delta in May and September 1979. 5 records from Cetacean sightings off Turkey 2006-2011. 1 records from Revision of the genus Allometopon Kertész (Diptera: Clusiidae). 2 records from Two new species of snailfishes of the genus Careproctus (Cottoidei: Liparidae) from the western North Pacific Ocean with a range extension of Careproctus brevipectoralis. 1144 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 112-681. 2 records from A new species of the hermit crab genus Diogenes Dana, 1851 (Decapoda: Anomura Diogenidae) from shallow coastal waters in Japan. 120 records from Plasm bearing foraminifera counts from M35/1_MSN1074. 493 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE255. 3 records from American Asteraceae-feeding Astrotischeria species with a highly modified, three-lobed valva in the male genitalia (Lepidoptera, Tischeriidae). 33 records from Données coléoptères de l'Association des Entomologistes de Picardie. 1232 records from (Table 1) Planktonic foraminifera community at DSDP Hole 94-608. 106 records from Total foraminifera counts from multinet M31/2_MSN890. 2535 records from Relative abundances of planktonic foraminifera in ODP Site 121-758 (Table 1). 932 records from CNAN/Araneae. 42 records from Estimated plankton abundance at station PS63/064-6. 11913 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 1074 records from (Table 2) Benthic foraminiferal species observed in the Quaternary samples from DSDP Hole 95-613. 1359 records from GEO Biodiversity Day. 2 records from New records of lampriform fishes (Teleostei: Lampriformes) from the Pacific coast of lower Central America, with comments on the diversity, taxonomy and distribution of the Lampriformes in the eastern Pacific Ocean. 8540 records from University of Nebraska State Museum Fish Collection. 9 records from Range table from planktonic foraminifers in ODP Hole 171-1052C. 72 records from Colección de Zoología Invertebrados - Helmintología. 20 records from Early Land Plants Today: Index of Liverworts & Hornworts 2013 - 2014. 2444 records from Algunas especies de anfibios y reptiles contenidos en el Proyecto de Norma Oficial Mexicana PROY-NOM-059-ECOL-2000. 64 records from Planktic foraminifera assemblage in sediment core SU90-I06. 41 records from Nineteen new species of Alycaeidae from Myanmar and Thailand (Gastropoda: Caenogastropoda: Cyclophoroidea). 79 records from Total foraminifera counts of multinet POS247/2_MSN1384. 17313 records from Fishes of INEP and NFH collections. 79288 records from Terrestrial and limnic invertebrates systematic collection, NTNU University Museum. 3 records from Distribution of Quinqueloculina sp. in sediment core 13200-073. 5 records from Revision of the genus Acylophorus Nordmann, 1837 from Madagascar and Mascarene Islands (Coleoptera: Staphylinidae: Staphylininae: Acylophorina). 256 records from (App 6) Relative contents of benthic foraminifera species in sediments from Core PS2718-6. 29 records from A taxonomic revision of the genus Xylota Meigen (Diptera: Syrphidae) in Korea. 2 records from Four new genera of Schizopteridae (Hemiptera: Heteroptera) from theAfrotropical and Neotropical regions. 206 records from MNA (Section of Genoa) and NIWA Invertebrate Collection - Ross Sea Tanaidacea. 600 records from Magnoliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 73 records from Swedish Malaise Trap Project (SMTP) - small Sciaroidea families. 73 records from Survey of slender naiad, Najas flexilis, in Loch of Butterstone and Loch of Craiglush. 1 records from A new pygmy species of box jellyfish (Cubozoa: Chirodropida) from sub-tropical Australia. 47 records from Sea lamprey distribution and abundance in the River Spey: phases II and III, 2001/2002. 167 records from Morfología funcional de mantos de rodolitos en el golfo de California, México. 392 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 115-708A. 1 records from ZUEC-CNI - Coleção de Cnidaria do Museu de Zoologia da UNICAMP. 136 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/042-2. 261 records from The Golden wasps collection (Chrysididae) at the Staatliches Museum für Naturkunde Stuttgart. 317 records from MUFAL herbarium - Museu de História Natural da Universidade Federal de Alagoas - Herbário Virtual REFLORA. 4028 records from Banco de datos de la ictiofauna del Río Bravo desde 1902 a 1992 en la colección ictiológica de la UANL. 60 records from Montana State University Billings. 9 records from Contribución a la distribución, ecología y estado de conservación de dos especies del género Sceloporus, endémicas de la región del Cabo, Baja California Sur. 333 records from renaturierter Main (Kemmern bei Bamberg). 155 records from (Appendix 1) Coral analysis and isostatic rebound effects from different Holes of IODP Expedition 310. 479 records from Geochemistry and sedimentology on core POS200/10_28-1. 413 records from Mammals in MZNA-VERT: biology of Arvicola sapidus in Navarra. PhD project, Juan Manuel Garde. 227 records from Observations Regelink Ecology and Landscape. 36665 records from Oskarshamn herbarium (OHN). 461 records from Distribución de peces dulceacuícolas introducidos en las cuencas del México central, con especial atención a las localidades dentro del área de distribución de los peces endémicos de la familia Goodeidae. 1 records from Michael Barkla's Observations. 4508 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica Tapachula). 3960 records from (Table 7) Occurrence of selected diatom species in ODP Hole 119-744A. 8333 records from Batsites inventory for England (1949-2011). 297 records from Abundance of calcareous dinoflagellates of sediment core GeoB1214-1. 103 records from Birdrace-Borussia_Zippammer-Bad Kreuznach. 37836 records from Isopoda (Interim dataset). 14 records from Ortopteroides de Oaxaca, México: Orthoptera, Mantodea y Phasmatodea. 12375 records from Données faune, flore et fonge du Conservatoire des espaces naturels de Picardie. 1 records from Données du/de la naturaliste VINCENT Sylvain provenant de la base de donnée du SINP Île-de-France CETTIA. 5044 records from Riqueza específica, distribución y abundancia de aves terrestres y marinas en Isla San José, Golfo de California, Baja California Sur, México. 972 records from Algae collection, Oslo (O) UiO. 8637 records from Relative abundance of benthic foraminifera in sediment core M5/2_KL15. 2 records from Taxonomic contribution to the genus Sphaerosyllis (Annelida: Syllidae: Exogoninae) in the Black Sea. 12 records from Chronicle of Nature - Phenology of Mammals of Tigirek State Nature Reserve. 29 records from Range table from planktonic foraminifers in ODP Hole 182-1130C. 2104 records from Données naturalistes de Jean-Paul LECHAPT. 3 records from Distribution of Quinqueloculina sp. in sediment core 12930-065. 899 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 6 records from Guinea-Bissau Herpetological Collection - IICT. 2 records from A new species and new records of minuta - group Gnamptogenys from Brazil (Hymenoptera: Formicidae). 967 records from Inventaire des Odonates. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 630 records from Códigos de barras del ADN de mamíferos topotipos de México Fase I: Noroeste mexicano. 3 records from Studies On Korean Stoneflies (Insecta: Plecoptera) With Descriptions Of Two New Species. 23 records from Species of Ancistrus (Siluriformes, Loricariidae) from Ecuador, with the description of a new species from the Amazon River Basin. 506 records from Crustáceos macrobénticos de la plataforma y talud continental del Golfo de México. 1 records from Validation of Tethya samaaii Ribeiro & Muricy, 2011, replacement name for the sponge Tethya rubra Samaai & Gibbons, 2005 (Demospongiae, Tethyida, Tethyidae). 12 records from Revision of the Oriental Chaetocnema species (Coleoptera, Chrysomelidae, Galerucinae, Alticini). 4 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 1460 records from (Table 3) Distribution of calcareous nannofossils at ODP Hole 125-782A. 34 records from Marine algal (seaweed) flora of Terceira Island, Azores. 368 records from (Table 4b) Distribution of benthic foraminifera of sediment core PS2212-3. 23 records from AlgaTerraMovies. 228 records from (Table 3) Planktonic foraminifer abundance of ODP Hole 162-980A. 143 records from (Table 2f) Nannofossil distribution chart of petroleum well Montara-2. 2 records from A review of the Barsine obsoleta species-group with description of a new species from Vietnam (Lepidoptera, Erebidae, Arctiinae). 7 records from (Table 1) Biometrics and lipid content of polar bear (Ursus maritimus) adipose tissue between 1991-2007. 18 records from Cape Cod Sea Turtle Release 2007 (aggregated per 1-degree cell). 60 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 278 records from Range table from benthic foraminifers in ODP Hole 182-1126B. 13 records from Benthic macrofauna abundance of sediment core 13200-047. 6279 records from SPC CoFish Fish Observations Palau 2007. 127 records from Epifauna community at Waarde and Saeftinghe (Westerschelde) in 1991. 2 records from A new genus and species of Onciderini Thomson, 1860 (Coleoptera: Cerambycidae: Lamiinae) from Ecuador, with notes on additional taxa. 73340 records from CSIRO, North West Shelf Demersal Marine Resources Study 1980-1997. 51 records from Shallow-water Demospongiae (Porifera) from Sodwana Bay, iSimangaliso Wetland Park, South Africa. 76 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 180 records from (Table 7) Distribution of the large, few-chambered Globigerinelloides species in DSDP Hole 79-545. 32482 records from Amphibiens et Reptiles de France métropolitaine (Enquête 1). 345 records from HUCPE - Herbário da Universidade Católica de Pernambuco. 52655 records from Natural England Marine Monitoring surveys. 705 records from Range table from benthic foraminifers in ODP Hole 139-857A. 81 records from (Table 4) Dinoflagellate cysts from sediment core PS1295-5. 186 records from Les spermaphytes de l'Herbier du Centre National de Floristique de Côte d'Ivoire: deuxième partie.. 1 records from A new species of the genus Protopolybia Ducke, 1905 (Hymenoptera, Vespidae, Polistinae), with taxonomic contributions to the exigua species-group. 194 records from POPA- Fisheries Observer Program of the Azores: Sea bird sightings in the Azores between 2004 and 2013 recorded by Biosphere Expedition. 8 records from Taxonomic revision of Agraphydrus Régimbart, 1903 I. China and Taiwan (Coleoptera: Hydrophilidae: Acidocerinae). 2754 records from Ground Beetle Recording Scheme - data verified via iRecord. 506 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/544-6. 126 records from Foraminifera species abundances from tow TT011_10-MOC71. 2482 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 2520 records from Phytoplankton abundance during G. M. Dannevig cruise GMD90/12. 8189 records from (Appendix A) Abundances of planktonic foraminifera in mid-Pleistocene sediments of ODP Site 184-1144 in the South China Sea. 242 records from (Table 1) Bottom fauna Metazoa in grab samples from the Namibia shelf in the area of Benguela upwelling. 16832 records from CUMV Fish Collection. 2090 records from MUST, Insecta. 112 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200320. 23 records from Distribution of planktic foraminifera of sediment core GIK23400-3. 270528 records from Données ONF faune-flore-fonge. 10 records from Distribution of planktic foraminifera of sediment core PS1235-1 at stadium 5.5. 48 records from Deutsche Schule Budapest. 2 records from Stenus maculifer CAMERON: eine Büchse der Pandora (Coleoptera, Staphylinidae) 365. Beitrag zur Kenntnis der Steninen. 18800 records from University of Tennessee Fungal Herbarium. 791 records from University of Michigan Museum of Zoology, Division of Mollusks. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_12-CTD139. 1928 records from Flora ficológica de la huasteca potosina. 126 records from Range table from benthic foraminifers in ODP Hole 144-874B. 56368 records from DASSH Data Archive Centre Academic Surveys. 1293 records from Herbier de Wallis et Futuna. 17 records from Revision of Nearctic Paramyia Williston (Diptera: Milichiidae). 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 121 records from Data collected during the expeditions of the e-learning projects Expedition Zeeleeuw and Planet Ocean. 142 records from Indo-Pacific bottlenose dolphin observations in the Clarence River 2003-2006. 1 records from Monotypic no longer: a new species of Panca Evans (Lepidoptera: Hesperiidae: Hesperiinae: Moncini) from South America. 109 records from Exkursion Ebertsheimer/Grünstädter Berg. 98037 records from University of Florida Invertebrate Paleontology. 71 records from The ant genus Strumigenys Smith, 1860 (Hymenoptera: Formicidae) in western North America North of Mexico. 10 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 136 records from Swedish Malaise Trap Project (SMTP) - Heloridae. 62 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 90 records from (Table 2) Occurrence of upper Maestrichtian to Eocene benthic foraminifers in ODP Hole 121-753A. 1 records from The millipede genus Tylopus Jeekel, 1968 (Diplopoda, Polydesmida, Paradoxosomatidae), with a key and descriptions of eight new species from Indochina. 123 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 112 records from Microzooplankton abundance measured on water bottle samples at station PS65/466-2. 201 records from Biodiversity of springs and rock seepages 2003. 2 records from Inventaire et regroupement de données Natura 2000. 562 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina (Peces). 10 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 1 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 1 records from A new riparian Mantidactylus (Brygoomantis) frog from the Tsaratanana and Manongarivo Massifs in northern Madagascar. 833 records from (Table 2) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Hole 120-748C. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-025. 72 records from Total foraminifera counts of multinet POS231/3_MSN1332. 1 records from Données du Geckos vert des Hauts (Phesulma borbonica) du Parc national de La Réunion. 595 records from Free-living plathelminthes of marine habitats near Wimereux (1990-1991). 961 records from Phytoplankton abundance and species composition in the Tyrrhenian Sea in November 1981. 2 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 128 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 3 records from New host-plants records of Afrotropical Gelechiidae (Lepidoptera), with description of three new species. 8539 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (Abejas). 1 records from Satellite Tracking of Hawksbill Turtle in West Sumbawa, Indonesia (aggregated per 1-degree cell). 1 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 7 records from Four new species of Diptilomiopinae from China (Acari: Eriophyoidea: Diptilomiopidae). 7 records from Siphonaptera and Phthiraptera Recording Scheme - records verified via iRecord. 59 records from Schulgelände SGD/Viersen. 1284 records from Données du/de la naturaliste ARNABOLDI Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 1260 records from Flora genérica de las gramíneas del estado de Tlaxcala. 52 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 153 records from Nannofossil abundance of Hole 84-570. 10129 records from TOPP Summary of SSM-derived Telemetry. 53 records from Leopard and Weddell seal program 1999/2002. 33 records from Données naturalistes de Ségolène FAUSTEN. 79 records from Meniscus Midges (Dixidae) of Ireland. 286 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 44781 records from Swiss National Bat Databank: Regional Coordination Western Switzerland (CCO). 2 records from Cryptic diversity across the Trans-Mexican Volcanic Belt of Mexico in the montane bunchgrass lizard Sceloporus subniger (Squamata: Phrynosomatidae). 96895 records from Données de l'AFB acquises selon le protocole de pêche complète à un ou plusieurs passages. 7168 records from Census of the species of Benin. Data mobilized in the framework of JRS Benin project and funded by JRS Biodiversity Foundation. 6 records from Sierraperla Jewett, 1954 (Plecoptera: Peltoperlidae), Distribution, Egg Morphology And Description Of A New Species. 15 records from Zambian Bat Collections Worldwide. 3 records from Two new species of Sweltsa (Plecoptera: Chloroperlidae) from China. 30356 records from Vascular plants of south-central China. 208 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 277 records from Inventario de gasterópodos terrestres y dulceacuícolas del área focal de Ixcan, Chiapas. 1 records from Discovery of the first leaf litter inhabiting flea beetles in Brazil (Coleoptera: Chrysomelidae: Galerucinae) with description of two new genera and three new species. 48 records from (Table 2) Benthic foraminifers at DSDP Hole 72-515A. 1 records from A new species of the greeneye genus Chlorophthalmus (Teleostei: Chlorophthalmidae) from the central North Pacific. 264 records from Swedish Malaise Trap Project (SMTP) - Mycetophilidae, Keroplatidae. 2016 records from Helmintos parásitos de peces del sureste de México. 260 records from Range table from benthic foraminifers in ODP Hole 159-959A. 396 records from Radiolaria assemblage in sediment core GIK23259-2. 63 records from Total foraminifera counts of multinet M21/4_MSN706. 268 records from Distribution of calcareous foraminifers in sediment core Well 6407/9-3. 42 records from BCCM/ULC Cyanobacteria culture collection at the University of Liège (ISO9001 certified). 711 records from Données naturalistes de Hervé BOUYON. 1071 records from Données de la collection Rousset -1947-2013. 57 records from (Table 2) Distribution of recurrent planktonic foraminifera at DSDP Hole 75-530A. 1 records from A New Free-living Marine Nematode Species of the Genus Graphonema (Nematoda: Chromadorida: Chromadoridae) from Antarctica. 41 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 109 records from Total foraminifera counts of multinet M21/2_MSN629. 90 records from Planktic foraminifera assemblage in sediment core GIK23065-2. 138 records from Total foraminifera counts of multinet POS247/2_MSN1372. 1 records from Dinoflagellate abundance of Hole 85-572C. 3912 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 31 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 2 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 9054 records from Highland bird data 2002 - 2003 - non-breeding records. 165 records from 1994-2020 Capercaillie Cold Searches Data, Scotland. 62 records from Total foraminifera counts from M35/1_MSN1061. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 2229 records from RNF - Données du Parc Naturel Régional du Vercors. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 1482 records from (Table 19) Ranges of benthic foraminifers from the late Neogene through the Pleistocene in ODP Hole 115-707A. 855 records from Insectes Hyménoptères Scollidés de France. 727 records from Family Geraniaceae in CSBG SB RAS herbarium collections (NS, NSK). 1801 records from The hoverfly collection (Diptera, Syrphidae) of the International Institute of Tropical Agriculture (IITA) at Calavi (Benin). 4717 records from Weddell Sea macrozoobenthos EASIZ I. 736 records from Distribution of planktic foraminifera in sediment core GIK23415-9. 4 records from A new South American species of Banasa Stål (Hemiptera: Heteroptera: Pentatomidae: Pentatominae): from e
Keywords: GBIF; biodiversity; species occurrences